Genomic characterization of historical Jinlingnan individuals: insights into genetic continuity and trans-Eurasian signals in eastern China - Shuyi Li; Yuchun Wang; Qu Shen; Jinguo Zan; Mengying Han; Zishuai Huang; Rui Wang; Xinyi Wang; Haifeng He; Le Tao; Hao Ma; Kongyang Zhu; et al. (Human Genetics, 2026)

Identification and transcriptional analysis of eight C1q genes in Takifugu obscurus during bacterial infection - Hao Wu; Ding-Yi Chen; Xiao-Han Li; Rui Shen; Zhe Zhao; Ying Huang (Fish & Shellfish Immunology, 2026)

Associations of prenatal per- and polyfluoroalkyl substance exposure with neonatal birth weight z-scores: The potential mediating role of maternal glucose homeostasis - Chun-Yong Wang; Zhen-Hua Li; Hai-Yang Weng; Xiao-Yu Zhao; Shao-Lei Pu; Meng-Na Zhu; Rui He; Xia-Juan Lu; Yu-Long Kan; Kai Huang; Guo-Peng Gao; Mao-Lin Chen; et al. (Environmental Pollution, 2026)

Photoelectrochemical CO2 reduction toward ethanol on silicon-based photocathodes with Cu-Cu2O and TCPPCu MOF heterointerface - Xin Li; Rui Chen; Ying Li; Jie Huang; Haiyan Zhu; Gang Shi (Chemical Engineering Journal, 2026)

Iterative precursor rebalancing improves phenazine-1-carboxylic acid production in engineered Pseudomonas chlororaphis - Sheng-Jie Yue; Peng Huang; Chen Song; Song Li; Rui Lian Yao; Wei Wang; Xue-Hong Zhang; Pablo I. Nikel; Hong-Bo Hu (Bioresource Technology, 2026)

Multi-scale mechanistic elucidation of hydrogen generation in chemical looping gasification of lignite using carbide slag - Xujie Luo; Senlin Dong; Jie Yang; Binbin He; Dongyang Li; Liping Ma; Bing Huang; Liang Chen; Qihong Cen; Heping Zeng; Rui Nie; Lan Shao (Journal of Environmental Chemical Engineering, 2026)

Breaking the Sabatier limit: Electrostatic-primed ion sieves-hydrogel for simultaneous solar desalination and ultrafast lithium extraction - Xinrong Huang; Rui Yang; Jun Xia; Qian Chen; Jinchi Li; Guangyong Zeng; Lihong Zhou; Yingtang Zhou; Hongbing Wang; Xiaoke Li (Desalination, 2026)

Polysiloxane-enabled dual-interphase engineering coupled with fluorescence diagnosis of Ni2+ dissolution for 4.6 V lithium metal batteries - Hankun Zhang; Jiacheng Yan; Benhua Wang; Jinqiang Gao; Chao Fu; Rui Zhang; Xiaowei Huang; Xiaowei Tang; Zhengzhao Yang; Kefei Wang; Bowei Ju; Xiangzhi Song; et al. (Chemical Engineering Journal, 2026)

Band degeneracy for enhanced thermoelectric performance in Zintl-phase devices - Yujie Huang; Kejia Liu; Huajian Wu; Haiqi Li; Rui Huang; Xiaofang Li; Shuankui Li; Yue Chen; Kai Guo; Chen Chen (Chemical Engineering Journal, 2026)

Binocular-depth-guided dual-view camera-LiDAR fusion for kiwifruit pose estimation in robotic harvesting - Shiao Niu; Leilei He; Qilin Gong; Qichen Huang; Ruichao Luo; Rui Li; Bao Zhou; Xiancun Zhou; Zhenchao Wu; Jinyong Chen; Xiaoxu Sun; Anastasia Grecheneva; et al. (Computers and Electronics in Agriculture, 2026)

A parallel electrical impedance tomography system for tissue-resolved imaging of relative stem conductivity dynamics in sunflower under PEG-induced stress - Liu-Deng Zhang; Ao-Wen Wang; Bing-Zhou Chen; Yang Xiang; Yu-Bin Lin; Chang Chen; Huan-Rui Ge; Ke-Lei Xia; Li-Feng Fan; Lan Huang; Zhong-Yi Wang (Biosystems Engineering, 2026)

Ecological risk assessment of 1,4-thioxane and its remediation by a synthetic microbiome based on a sulfur transformation system: From multi-omics to water application - Xu Yang; Ai-de Peng; Yong-han Huang; Jia-hao Cheng; Hao-tian Zhong; Hai-tang Zhou; Pei-qi Liu; Xiao-hui Ji; Chen Li; Sheng-rui Zhang; Jin-long Lai; Xue-gang Luo (Water Research, 2026)

Differential effects of conventional and biodegradable microplastics on carbon and nitrogen transformation and greenhouse gas emissions in Cd-contaminated riparian sediments: Responses of microbial community structure - Haojie Chen; Danlian Huang; Wei Zhou; Yang Lei; Hai Huang; Lingshi Yin; Ruihao Xiao; Rui Deng; Guangfu Wang; Wenbo Xu (Water Research, 2026)

Critical review on strategies for the removal of antibiotics from water and wastewater: Present situation, challenges, and perspective - Ruiwu Zhou; Wei Pan; Weichao Huang; Ping Yu; Binrui Chen; Ruizhe Zhao; Lirong Chen; Rui Tang (Process Safety and Environmental Protection, 2026)

Anti-lipotoxic alkaloids from the roots of Polyalthia cerasoides - Feifei Liu; Xinyi Liu; Yue Chen; Rui Su; Meilan Zhou; Jin Liu; Zhongping Jiang; Yong Rao; Ling Huang (Phytochemistry, 2026)

Insights into the fate and dynamics of antibiotic resistance in multidrug-resistant Bacillus cereus during in vitro simulated gastrointestinal digestion - Wen-Li Shi; Juan Zhang; Rui Huang; Yan Qi; Juan Wang; Yu Ding; Jia-Jun Yan; Quan Zhou; Zi-Hui Chen; Zhi-Hang Chen; Ai-Min Jiang; Ling Chen; et al. (Food Research International, 2026)

CXCL8 is associated with aflatoxin B1–triggered injury and caspase-3 activation in porcine kidney epithelial PK15 cells: integrated transcriptomics and CRISPR/Cas9 knockout - Jianlin Yuan; Yuhan Ma; Jinfeng Li; Xizhu Chen; Yiping Wen; Rui Wu; Xinfeng Hang; Heng Huang; Senyan Du; Yiping Wang; Qi-Gui Yan; Xiaobo Huang; et al. (Food and Chemical Toxicology, 2026)

Bionic snail-shell-shaped evaporator featuring silver-nanoparticle-decorated carbon nanotubes for efficient solar desalination - Yutao Huang; Zhihong Chen; Xuan Wang; Xin Guan; Jia Zeng; Rui Li; Leitao Han (Chemical Engineering Journal, 2026)

Effect of the thickness of overlying soil on the location of trailing edge cracks in soil–bedrock landslides induced by water softening - Yun-kang Rao; Jia-xin Chang; Hai-ying Fu; Tao Yang; Huai-lin Chen; Zhe Zhang; Yi Yang; Rui Huang (Bulletin of Engineering Geology and the Environment, 2026)

Decoction-derived bioactive nanoparticles of Lycopodium japonicum Thunb. attenuate knee osteoarthritis by regulating MAPK/ERK signaling - Xiaohui Chen; Gang Liang; Liangwei Wang; Zhilang Xie; Zhongpan Li; Yulin Xiang; Rongzhu Li; Fulan Zhao; Xiaojun Chen; Rui Huang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

A practical guide to investigating biomolecular condensates: a comment from the plant community - Jiaxuan Peng; Jaime Agudo-Canalejo; Monika Chodasiewicz; Daniël Van Damme; Vangelis Daskalakis; Manuel González-Fuente; Rui Gao; Emmanouela Filippidi; Hongwei Guo; Shengbo He; Kai Huang; Shuai Huang; et al. (Science China Life Sciences, 2026)
Biomolecular condensates formed through phase separation have emerged as a central principle of cellular organization, enabling the dynamic regulation of gene expression, signaling, metabolism, and stress responses. While early conceptual advances in condensate biology have largely originated from animal and in vitro systems, plant cells present a unique set of biological and technical challenges, including rigid cell walls, turgor pressure, plastid autofluorescence, complex endomembrane organization, and acute environmental responsiveness. These distinctive features impede the direct transfer of existing methodologies and drive the development of heterogeneous experimental practices. In this community comment, we present a comprehensive methodological framework for studying biomolecular condensates in plants, spanning in silico prediction, in vitro reconstitution, molecular dynamics simulations, live-cell and super-resolution imaging, material property measurements, membrane-associated condensates, and synthetic condensate engineering. We highlight best practices, common pitfalls, and plant-specific considerations, emphasizing the need for orthogonal validation, quantitative interpretation, and physiological relevance. By consolidating current methodologies and articulating shared principles, this review aims to establish a foundation for rigorous, reproducible, and conceptually coherent research in condensate biology of plants and beyond, with emerging implications for crop genetic improvement and synthetic biology applications.

Prediction and critical feature analysis for coronary artery calcification progression - Ran Liu; Gaojian Yang; Wenyu Huang; Junyan Zhang; Yuting Lei; Rui Zhang; Zhongxiu Chen; Yong He; Hongmei Yan; Kaiyue Diao (Medical & Biological Engineering & Computing, 2026)

Recognition of kiwifruit pruning position based on vine segmentation and dormant bud detection with their planar distribution - Shuolin Kong; Bo Jia; Qichen Huang; Juncai Huang; Rui Li; Bao Zhou; Xiancun Zhou; Zhenchao Wu; Jinyong Chen; Xiaoxu Sun; Dateng Zheng; Davut Karayel; et al. (Computers and Electronics in Agriculture, 2026)

A legacy pollutant deciphered by multiomics toxicology and targeted remediation by a synthetic microbial consortium: a case study of 2-chloroacetophenone from abandoned chemical weapons - Xu Yang; Ai-De Peng; Jia-Hao Cheng; Yong-Han Huang; Hao-Tian Zhong; Hai-Tang Zhou; Pei-Qi Liu; Xiao-Hui Ji; Chen Li; Sheng-Rui Zhang; Jin-Long Lai; Xue-Gang Luo; et al. (Water Research, 2026)

Aeolian transport of evaporite minerals in Utopia Planitia: insights from Qaidam Basin spectral analogs - Jianxun Shen; Honglei Lin; Zhaopeng Chen; Xue Guo; Yuqi Wang; Yizhong Zhang; Li Liu; Chengxiang Huang; Enze Wang; Rui Chang; Xuesen Xu; Zhicheng Cui; et al. (Science Bulletin, 2026)

Near-real-time mapping for causal agents of forest disturbances in China using harmonized Landsat and Sentinel-2 dataset - Ronghua Liao; Chengcheng Guo; Lingkun Chen; Yulin Jiang; Yuchen Tao; Jiani Liao; Rui Lu; Huaguo Huang; Zhou Shi; Su Ye (Remote Sensing of Environment, 2026)

Long term salinity acclimation buffers combined impacts of heat–salinity on Daphnia by reconfiguring osmoregulatory transcription - Jing Huang; Yalin Chen; Zihao Jin; Rui Wu; Zhou Yang (Marine Environmental Research, 2026)

Improving spatiotemporal assessment of watershed soil redistribution by integrating source-sink theory into a multi-model framework - Rui Tan; Yu Tao; Geng Guo; Kaiwen Huang; Zicheng Liu; Lin Chen; Xin Liu; Jie Lin (Journal of Hydrology, 2026)

MFN2-mediated remodelling of ER-mitochondria communication alleviates ochratoxin A-induced hepatocyte ferroptosis by enhancing mitophagy - Zi-Yan Hu; Rui-Qi Liu; Yu-Xuan Ouyang; Ming-Shan Chen; Jia-Xin Wang; Ming Lou; Yi-Feng Huang; Hong-Li Si; Fu-Wei Jiang; Zhuo-Yu Liu; Yi-Bo Wang; Li Wang; et al. (Journal of Hazardous Materials, 2026)

From acute defense to prolonged metabolic homeostasis: Insights into microalgae responses to PVC microplastic exposure - Jia Liang; Xiao Tan; Jiawei Li; J. Paul Chen; Yuanyuan Tang; Zhipeng Duan; Jiang Huang; Rui Zhu (Journal of Hazardous Materials, 2026)

Particulate matter concentration and population exposure assessment in metro systems: a case study of Hangzhou - Chen He; Rui Zhang; Xiyao Chen; Keliang Li; Ben Ye; Lingtong Huang; Shupeng Zhu; Weijun Li (Journal of Environmental Sciences, 2026)

Optimizing pe+pH via integrated water management and phosphorus fertilization enhances phytoextraction of Cd/As by rice plant in contaminated paddy soils - Rui Huang; Yunhe Xie; Xin Wang; Wei Wei; Bingyu Li; Jingmin Yang; Haoyu Chen; Saihua Liu; Xionghui Ji (Journal of Environmental Sciences, 2026)

Discovery of phage lysin against Vibrio parahaemolyticus and characterization of its antibacterial activity - Rui Zhang; Jiajun He; Fangfang Yao; Fangyuan Chen; Hongping Wei; Shengfu Huang; Yuhong Li (International Journal of Food Microbiology, 2026)

Effective photodynamic inactivation of curcumin in combination with ethylenediaminetetraacetic acid against Burkholderia gladioli pathovar cocovenenans - Xiu-Xia Tian; Jia-Jun Yan; Rui Huang; Quan Zhou; Qi-Ying Zeng; Yu-Ming Jiang; Zi-Hui Chen; Hai-Yan Wang; Bai-Sheng Li; Yong-Ning Wu; Wei-Liang Wu (Food Research International, 2026)

Eccentric coaxial wet-spun magnetic composite actuators with decoupled magneto-pneumatic shape-morphing for biomedical applications - Ping-an Yang; Yixuan Han; Chunyan Mo; Mengjie Shou; Rui Li; Yi Lu; Decheng Wu; Qiao Chen; Zhiwei Huang (Chemical Engineering Journal, 2026)

Corrigendum to “A self-limiting swelling hydrogel with covalent anchoring for durable vascular embolization” [Chemical Engineering Journal 532 (2026) 174382] - Rong Wang; Rui Zhang; Siying Li; Yuxuan Huang; Jingying Yan; Yuqing Gu; Qi Jiang; Xuri Chen; Jinchun Ye; Qianqian Zhu; Xianzhu Zhang; Xiaozhao Wang; et al. (Chemical Engineering Journal, 2026)

Electron-networking Cu single atom-spurred Ru clusters for anion exchange membrane water electrolysis - Zihao Zhou; Rui Qin; Tingjie Mao; Pinlin Wang; Zhongliang Huang; Ting-shan Chan; Yu-cheng Huang; Zhiwei Hu; Xiaoqing Huang; Nanjun Chen; Yunhua Li (Chemical Engineering Journal, 2026)

Analysis of Arbuscular Mycorrhizal Fungal Community in Soil of Sugarcane at Different Tillage Depths - Qun-Qing Huang; Sheng Wang; Ying-Jie Nong; Kai-Mao Zhong; Yi-Cheng Su; Xiao-Juan Qin; Jin-Lian Zhang; Yi-Hao Kang; Ting-Su Chen; Shi-Yuan Zeng; Xi-Chao Deng; Ming-Guo Jiang; et al. (Sugar Tech, 2026)

Compartmental pH regulation in cancer and antitumor immunity: therapeutic opportunities and challenges - Fangquan Chen; Xiutao Cai; Qile Zhou; Zhen Huang; Jie Wang; Rui Kang; Daolin Tang; Jiao Liu (Apoptosis, 2026)

Advances in oral delivery systems for alpha-linolenic acid: mechanisms, bioavailability, and applications in functional foods - Fazhan Zhong; Qianchun Deng; Shangwen Chen; Rui Fang; Yawen Huang; Dengfeng Peng; Xia Xiang; Yashu Chen; Li Chen; Xiao Lin; Ziyu Deng (Critical Reviews in Food Science and Nutrition, 2026)

Multidimensional effects of personalized exercise intervention in type 2 diabetes: a randomized controlled trial - Dan Liu; Di Cheng; Qinyi Wang; Ying Zhang; Piao Kang; Chufan Zhao; Hongfeng Mao; Jing Qu; Sheng Liu; Xiaojing Gao; Rui Han; Jingyi Guo; et al. (Science Bulletin, 2026)

Pancancer pro-angiogenic atlas unravels tumor-educated pericyte-augmented anti-angiogenic resistance - Yongqiang Zheng; Hui Sun; Zhe Fu; Haojie Chen; Guangyao Cai; Xin Huang; Yi-Qian Pan; Kai Yu; Ping Chen; Zhuoran Liang; Junteng Li; Jiamin Hu; et al. (Science Bulletin, 2026)

Os79, a UDP‐Glycosyltransferase, negatively regulates cadmium tolerance and accumulation in rice - Rui Guo; Hao Yu Wang; Chong Wei Zhong; Rong Rong Ma; Jiu Huang; Jin Chen; Xian Jiao Guan; Lu Zheng; Ren Fang Shen; Ming Qing Liu; Xiao Fang Zhu (Journal of Hazardous Materials, 2026)

Dual-function photosensitive bacterial cellulose film for real-time meat freshness monitoring and rapid sterilization - Rui Chen; Yiwen Xie; Yunyan Bai; Kerang Huang; Xuemei Liao; Yulin Liu; Rong Wang (Food Control, 2026)

Construction and evaluation of injectable enzyme-crosslinked emodin liposome nanohydrogel: Mechanistic study on inhibiting pyroptosis for the treatment of rheumatoid arthritis - Liangwei Wang; Zhongpan Li; Zhilang Xie; Xianghan Hou; Rongzhu Li; Yulin Xiang; Xiaohui Chen; Fulan Zhao; Jiaqi Wu; Guoyou Wang; Rui Huang (Chemical Engineering Journal, 2026)

Bilayer encapsulation strategy enabled ultra-stretchable electronic skin for human-machine interaction - Miao Kong; Yuxin Chen; Shengwei Gao; Xue Wang; Jiaxin Zhuang; Panqi Huang; Zifan Li; Xu Wang; Zilin Wang; Yuqing Zhang; Ji Cheng; Ruiqi Guo; et al. (Chemical Engineering Journal, 2026)

Multifunctional CHB@CM hydrogel for periodontal therapy attenuates the progression of periodontitis-aggravated chronic kidney disease by regulating the TLR2/4/NF-κB signaling pathway - Yuanxiang Liu; Lei Chen; Zhipeng Li; Ruoxuan Huang; Chengwu Liu; Rui Guo; Runheng Liu; Chuan Zou (Chemical Engineering Journal, 2026)

Statistical optimization of fungal chitosan production by Aspergillus niger using agro-industrial residues - Fengwei Yin; Jie Huang; Rui Wang; Yao Chen; Xiaolong Sun; Yongqian Fu (Biocatalysis and Agricultural Biotechnology, 2026)

Genome-wide association analysis and candidate gene identification for plant height in Shanxi local foxtail millet varieties - Wei Zhou; Huibin Qin; Haigang Wang; Hui Zhi; Rui Huang; Sen Hou; Junjie Wang; Ling Chen; Xiang Tian; Zhijun Qiao; Zhixin Mu; Xianmin Diao (Theoretical and Applied Genetics, 2026)

Fe-N-C-supported LaFeO3 heterojunction electrodes for efficient copper and fluoride removal in symmetric capacitive deionization - Shaojian Xie; Yujia Wang; Rui Zhang; Lei Huang; Jia Yan; Zhenxin Chen; Hongguo Zhang; Meng Li; Hongbo Zeng (Water Research, 2026)

Biofilm-suspension syntrophy drives synergistic electro-fermentation through engineered spatial division of labor for concurrent carbon recovery and pollutant degradation - Jiayu Gu; Jiying Guo; Rui Peng; Yang Wu; Min Long; Xiong Zheng; Haining Huang; Yinguang Chen (Water Research, 2026)

Report on the complete mitochondrial genome of the critically endangered and endemic Lauraceae plant Syndiclis anlungensis in China - Lang Huang; Dongzhen Jiang; Yanbing Yang; Rui Chen; Zhi Li; Lei Zhou; Xu Xiao (Plant Gene, 2026)

Self-supported cube-like Cu nanoparticles with in-situ growth for efficient CO2 electroreduction to hydrocarbons - Peijun Li; Weicong Xu; Xing Wang; Chao Liu; Anze Ning; Qingwen Chen; WulejiasiI Aerxin; Tao Li; Haowei Huang; Rui Xiao (Journal of Environmental Chemical Engineering, 2026)

Magnesium isotope geochemistry in continental flood basalts: implications for mantle source heterogeneity - Sakine Moradi; Lie-Meng Chen; Peter C. Lightfoot; Kang-Jun Huang; Qiao Su; Song-Yue Yu; Li-Juan Zhu; Rui-Zhong Hu (Geochimica et Cosmochimica Acta, 2026)

Systemic crosstalk between liver and brain is associated with microplastic-induced neurobehavioral toxicity in zebrafish - Zhimin Xu; Zheng Lin; Yifan Wang; Lei Wang; Runtong Huang; Rui Du; Xinya Kang; Xueqing Chen; Shaohua She; Zhihao Xu; Shuai Xiao; Renqiang Yu (Environmental Pollution, 2026)

Transdermal delivery of small zwitterionic amorphous solid dispersion to increase solubility and penetrate the stratum corneum for psoriasis therapy - Xiang Zhou; Jiahui Ma; Lanlan Wang; Dongyu Zhang; Dongyue Ding; Rui Xu; Ke Wang; Junlong Qi; Yinan Zhong; Dechun Huang; Wei Chen (Chemical Engineering Journal, 2026)

Restraining grain growth and constructing defects in olivine-type silicate as high-performance cathode for rechargeable magnesium batteries - Jie Xu; Minjie Zhang; Rui Pu; Guangsheng Huang; Jingchao Zhang; Jianrong Zeng; Yanan Chen; Jingfeng Wang; Jili Yue; Fusheng Pan (Chemical Engineering Journal, 2026)

Corrigendum to: “Photothermal modulation of the regenerative microenvironment for reversing optic nerve injury” [Chem. Eng. J. 524 (2025) 169698] - Kexin Tan; Jiayu Wang; Qianyue Zhang; Shuo Wu; Haiyang Zhang; Yusha Liu; Zhaohan Qu; Siwei Liu; Rui Huang; Yan Liu; Yang Wang; Yingzhi Chen; et al. (Chemical Engineering Journal, 2026)

Multifunctional interface engineering enables high efficiency of semi-transparent CsPbBr3 solar cells - Ankang Shu; Mingming Li; Jiawei Song; Zhengyang Li; Qian Wang; Shangwei Huang; Jiahao Cheng; Wenjian Shen; Cong Geng; Rui Chen; Guijie Liang; Jun Yao; et al. (Chemical Engineering Journal, 2026)

Boosting longan seed starch-flavonol complex formation via cold plasma: Structural, functional, and mechanistic insights - Rui Huang; Rui He; Xiaoyu Lin; Jiao Chen; Yun Chen; Tao Yang (Carbohydrate Polymers, 2026)

Dual Low-b-value-driven U-shaped fusion GAN for synthesizing high-b-value prostate DWI - Rui Feng; Qun Huang; Aiping Chen; Chuanbing Wang; Leilei Zhou; Jingjing Xu; Xiaodong Wang; Da Cao; Xiuhan Li; Wei Wang (Physical and Engineering Sciences in Medicine, 2026)

Optimizing drug delivery in smart pharmacies: a novel framework of multi-stage grasping network combined with adaptive robotics mechanism - Rui Tang; Shirong Guo; Yuhang Qiu; Honghui Chen; Lujin Huang; Ming Yong; Linfu Zhou; Liquan Guo (Medical & Biological Engineering & Computing, 2026)

Synthesis, anticancer activity and molecular docking study of triphenylphosphonium-linked derivatives of oleanolic acid - Deshang Li; Bo Wang; Rui Wang; Jianjun Huang; Ruofan Chen; Yi Li; Na Wang; Qianqian Wang; Chenmeng Xu; Wim Dehaen; Qiyong Huai (Natural Product Research, 2026)

Microbiota-responsive BmMBF2-11 limits dysbiosis and promotes intestinal immune homeostasis in the silkworm - Qingxiu He; Rui Yang; Huawei Liu; Huanan Zhu; Yu Zhang; Hao Chen; Qingsong Liu; Guangcheng Huang; Qingyou Xia; Ping Zhao (Insect Biochemistry and Molecular Biology, 2026)

Mechanical-thermal -electrical-magnetic integration in aramid composites via binary inorganic synergy - Junchao Ren; Chenglei Huang; Rui Tan; Jianlong Chen; Mengde Huang; Shijing Song; Chengyu Yu; Hanwu Lei; Lu Wang; Bin Li; Qingfa Zhang (Chemical Engineering Journal, 2026)

Multi-source remote sensing unveils hydrological dynamics and drought escalation in Central Asia’s arid regions - Yuhao Wang; Zhijie Zheng; Guofeng Zhu; Enwei Huang; Gaojia Meng; Siyu Lu; Dongdong Qiu; Longhu Chen; Rui Li; Yinying Jiao; Ling Zhao; Xiaoyu Qi; et al. (Journal of Geographical Sciences, 2026)

Responses of Phaeodactylum tricornutum to short-chain chlorinated paraffins: growth inhibition, photosynthetic damage and oxidative stress - Rui Shi; Wei Chen; Yujun Hu; Bingjian Chen; Xiaoxiao Yu; Hui Huang; Dan Wang; Shunxin Hu (Frontiers in Marine Science, 2026)
Introduction Short-chain chlorinated paraffins (SCCPs) have garnered increased attention due to higher persistence, bioaccumulation, long-distance transportation potential, and heightened toxicity to aquatic species and mammals. Methods This paper evaluated the toxic effects of SCCPs on P. tricornutum during a 96-hour acute exposure experiment, focusing on growth inhibition, photosynthetic parameters, and oxidative stress responses. Results Results showed that at the environmental concentration (0.001 mg/L), SCCPs exerted no significant effects on the growth and photosynthesis of P. tricornutum . However, higher concentrations (2, 4, and 8 mg/L) exposure resulted in a pronounced, dose-dependent growth inhibition, with inhibition rates reaching 37.43%, 53.25%, and 54.47% (p < 0.05), respectively. SCCPs stress disrupted the photosynthetic system, leading to reduction in the contents of chlorophyll a, chlorophyll c and carotenoids. Key photosynthetic pigments were depleted, and Photosystem II (PSII) efficiency (Fv/Fm, Y(II), rETRmax) was markedly suppressed. Furthermore, SCCPs exposure induced oxidative damage, as evidenced by elevated reactive oxygen species (ROS) and malondialdehyde (MDA) levels. Mitochondrial damage led to insufficient energy supply, resulting in decreased antioxidant enzyme activity. Discussion Collectively, these findings establish that high concentrations of SCCPs inhibit algal growth and photosynthesis through a dual mechanism involving direct photosynthetic disruption and the induction of oxidative damage.

Multi-omics analysis provides genetic evidence for the involvement of cell adhesion pathway in the pathogenesis of biliary atresia - Rui Dong; Jinhang Zhu; Chunjing Ye; Fenglong Sun; Cong Huai; Wei Zhou; Jiajie Zhu; Xiaoqi Feng; Qiange Xiao; Deqian Chen; Yifan Yang; Ran Yang; et al. (Science China Life Sciences, 2026)

Unveiling the environmental fate and risks of non-heterocyclic sulfacetamide: From a novel degradation mechanism to microecological effects - Guoqiang Zhao; Wenjing Chen; Wanying Zhang; Rui Zhang; Xing Huang (Water Research, 2026)

Thioredoxin PgTRX acts as a protein elicitor to suppress green mold in citrus fruit via modulation of glutathione metabolism - Rong Zhu; Ou Chen; Yao Xu; Rui Huang; Wenjun Wang; Jian Ming; Kaifang Zeng (Postharvest Biology and Technology, 2026)

SgPAP27b, a purple acid phosphatase, confers aluminum tolerance in Stylosanthes guianensis through membrane lipid remodeling - Jianyu Zhang; Jinhui Lv; Chun Liu; Ranran Xu; Yu Liu; Rui Huang; Rongshu Dong; Pandao Liu; Zhijian Chen (Journal of Hazardous Materials, 2026)

Unveiling the mechanistic in polarized light excited dissolved organic matter degrading contaminant: Energy transfer or electron transfer - Gang Wang; Pengcheng Huang; Qiyuan Sun; Feifeng Wang; Jiejie Chen; Yayin Jiang; Yuyi Zheng; Rui Ding; Tianfang Zhang; Bin Zheng; Zhiqiang Zhang (Journal of Environmental Chemical Engineering, 2026)

Insight into the enhancement effect of pristine and amino-functionalized MWCNTs@SiO2 on the CO2 absorption and solar-driven regeneration performance of alkaline deep eutectic solvent based nanofluid system - Wei Wang; Yang Tang; Yi-Ming Chen; Rui-Rui Zhou; Zhang-Mao Hu; Jin-Cheng Huang (Journal of Environmental Chemical Engineering, 2026)

Regenerative treatment of aquatic pollutants of microplastic and antibiotics based on synergistic effect of magnetic biochar/protonated g-C3N4 - Zifeng Li; Rui Shan; Guoqiang Wei; Leyi Huang; Dong Liang; Haoran Yuan; Yong Chen (Journal of Environmental Chemical Engineering, 2026)

Effective recovery of Dy from LiCl-KCl molten salt via controlled potential on Ga electrode: Mechanism, kinetics and thermodynamics of electrode reaction - Yuying Xiao; Wenlong Li; Rui Li; Ziqin Huang; Ming Gong; Jiandong Li; Ji Wang; Lifeng Chen; Shunyan Ning; Xiangbiao Yin; Wei Han; Yuezhou Wei (Journal of Environmental Chemical Engineering, 2026)

The structural and transcriptional basis of carboxylesterase-mediated λ-cyhalothrin resistance in Spodoptera litura - Jun Li; Xiaodan Huang; Mengqing Deng; Jiemeng Chen; Linjie Zhou; Xiyue Xu; Xinyu Zhao; Rui Peng; Zhiming Yang; Kai Lu (Insect Biochemistry and Molecular Biology, 2026)

Environmental contexts mediate the dual impacts of snow cover on vegetation green-up: A key challenge of phenological prediction under climate change - Zizhen Dong; Likai Zhu; Lingwei Chen; Rui Huang; Cuiyutong Yang; Jijun Meng; Min Liu (Global and Planetary Change, 2026)

Curcumin-derived smart anti-corrosion coating for early damage warning and active protection in diverse lighting and corrosive environments - Jinke Wang; Xin Guo; Congshu Huang; Danni Shang; Zhibin Chen; Rui Tian; Lingwei Ma; Dawei Zhang (Chemical Engineering Journal, 2026)

Study on the effect of pore structure on water retention properties of compacted loess under wetting and drying cycle conditions - Zhiyong Zhang; Weixing Bao; Lei Tian; Zhiming Huang; Xiaolin Guan; Rui Chen (Bulletin of Engineering Geology and the Environment, 2026)

Design, synthesis and antitumor activity of triphenylphosphonium-linked derivatives of quinazolinone - Qianqian Wang; Ruofan Chen; Rui Wang; Jianjun Huang; Yinuo Xu; Na Wang; Deshang Li; Chenmeng Xu; Bo Wang; Yi Li; Wim Dehaen; Qiyong Huai (Natural Product Research, 2026)

Sustainable electronics manufacturing using environmentally safe short chain fluorinated Gemini surfactants for high efficiency printed circuit board cleaning - Yunye Huang; Lewen Huang; Chen Zhou; Danni Tang; Xiangyu Yin; Longqiang Xiao; Rui Zhao; Linxi Hou (Journal of Cleaner Production, 2026)

Enhancing rice yield and nitrogen use efficiency through OsRAV1 expression and crop management - Yingbo Gao; Haiyan Chao; Xinyi Zhao; Xin Liu; Chang Liu; Guanda Hu; Xueqin Chen; Guowei Wang; Dunliang Wang; Rui Li; Juan Zhou; Xiaoxiang Zhang; et al. (Field Crops Research, 2026)

A self-limiting swelling hydrogel with covalent anchoring for durable vascular embolization - Rong Wang; Rui Zhang; Siying Li; Yuxuan Huang; Jingying Yan; Yuqing Gu; Qi Jiang; Xuri Chen; Jinchun Ye; Qianqian Zhu; Xianzhu Zhang; Xiaozhao Wang; et al. (Chemical Engineering Journal, 2026)

Damages of aged-PVC microplastics exceed the enhanced resistance of chlorella pyrenoidosa induced by phosphorus limitation - Xiao Tan; Lv Wang; Chao Xing; Zhipeng Duan; Jia Liang; Rui Zhu; Jiang Huang; Shichao Chen; Yijia Wei (Aquatic Toxicology, 2026)

A multi-layer coupling framework for hydrodynamic simulation of underground station flooding - Dong-Mei Zhang; Hai-Yun Li; Wen-Ding Zhou; Si-Rui Chen; Zhong-Kai Huang (Tunnelling and Underground Space Technology, 2026)

Nitrogen fertilizer strategies modulate gaseous nitrogen losses and improve maize yield and nitrogen use efficiency under saline-alkali stress in coastal reclaimed farmland - Xiaoqing Wang; Jiayi Xie; Wenjing Li; Lijie Pu; Pengjun Chen; Jijun Han; Chenliang Du; Sihua Huang; Rui Zhang; Rui Zhong; Ye Yuan; Jiahao Zhai; et al. (Soil and Tillage Research, 2026)

QuaFT: Quality-guided semantic fault intelligence under corrupted industrial data - Lu Ning; Rui Wang; Xiaoran Wei; Hao Huang; Zonghan Zhang; Zehua Chen; Xiaolu Liu; Bo Zhang; Yao Liu; Hao Gong; Kai Song (Process Safety and Environmental Protection, 2026)

Species delimitation within a taxonomically complex group: An example from the genus Apodemus (Rodentia: Muridae) - Xuan Pan; Buqing Peng; Xuming Wang; Zhongzheng Chen; Hao Cheng; Rui Liao; Chia-Lung Huang; Jiatang Li; Shaoying Liu (Molecular Phylogenetics and Evolution, 2026)

Insights into the molecular mechanism driving transformation and detoxification of erythromycin in anoxic biofilters - Zhihui Chen; Ying Zhao; Lili Jin; Rui Ma; Han Zhao; Hongqiang Ren; Hui Huang (Journal of Hazardous Materials, 2026)

Investigation on the deodorization effect and mechanism of deodorant-rubber asphalt - Hui Wang; Tao Chen; Huiyun Wu; Junwei Xiang; Yujie Huang; Shuihui Wu; Juan Xie; Pu Zhao; Weiyong Rui (Fuel, 2026)

National-scale insights into occurrence, health risks, and potential sources of 1,4-dioxane in drinking water of China - Feng Yang; Lulu Zhang; Xiaodong Hu; Rui Huang; Chunmei Wang; Yubai Chen; Aimin Li; Qing Zhou; Xiuwen Li; Peng Shi (Environmental Pollution, 2026)

Isothiazolinone biocide aggravate disinfection-resistant bacterial fouling on reverse osmosis membranes - Yu-Qing Xu; Zheng-Yang Huo; Yuan Bai; Yun Wang; Wen-Long Wang; Hao-Bin Wang; Yu-Jia Gao; Rui-Ning Wang; Chen-Yu Li; Han Liu; Wei E. Huang; Hong-Ying Hu; et al. (Desalination, 2026)

Defect passivation with Pb for high-performance Sb2S3 solar cells via vapor transport deposition - Gan Huang; Xin-Yi Cai; Hu Li; Jin-Rui Cai; Ying-Sen Xia; Zhi-Ping Huang; Li-Mei Lin; Fu-Bao Gong; Shui-Yuan Chen; Gui-Lin Chen (Chemical Engineering Journal, 2026)

Short-term and long-term effects of outdoor artificial light at night on reproductive hormones among infertile women from a preconception cohort study - Wenbin Fang; Cun Huang; Ying Tang; Mengdie Li; Yaning Sun; Yanlan Tang; Yinyin Chen; Yawen Cao; Jiqi Fang; Kunjing He; Jing Shen; Zhiyuan Huang; et al. (International Journal of Biometeorology, 2026)

An unconventional topology of betacoronavirus membrane protein drives viral assembly - Rui Lyu; Kaili Li; Lingjiao Xiang; Yingjian Li; Yaotian Liang; Xue Tan; Xiaoya Huang; Yu Chen; Hongyu Deng; Junjie Hu (Science Bulletin, 2026)

Sustainable MXene-mediated in-situ ZnO/cellulose composites via green fabrication with enhanced mechanical durability, antimicrobial activity, and EMI shielding performance - Yangyang Liu; Rui Tan; Jianlong Chen; Mengde Huang; Junchao Ren; Lu Wang; Qingfa Zhang (Journal of Cleaner Production, 2026)

Beyond the surface: how dissolved organic matter recasts the biogeochemical behaviors of micro- and nanoplastics in aquatic environments - Haojie Chen; Danlian Huang; Ruihao Xiao; Wei Zhou; Lingshi Yin; Rui Deng; Hai Huang; Yang Lei; Ruijin Li (Gondwana Research, 2026)

Effect of extrusion parameters on the quality of extruded reconstituted konjac glucomannan Rice - Rui Lai; Jie Liu; Hanxiao Qin; Qing Li; Yong Chen; Wenxuan Pan; Jikai Zhao; Qing Huang; Hongzhou An; Qian Lin; Yanru Li (Food Chemistry, 2026)

Composite hydrogel microspheres modulate intestinal inflammation via releasing HA modified liposomes@4-OI targeting M1 macrophages - Shuanghong Yang; Ze Li; Guiwen Qu; Liting Deng; Liuqing Dou; Sicheng Li; Yitian Teng; Luqiao Huang; Haohui Li; Kang Chen; Jinpeng Zhang; Rui Ma; et al. (Chemical Engineering Journal, 2026)

Ligation-mediated circuit-driven cascade amplification with high utilization rate of template for lncRNA MALAT1 detection in cancer mice tissues - Yuyan Huang; Fan Huang; Qianqian Du; Rui Yu; Jingfeng Lan; Junwei Luo; Hongli Chen; Huige Zhang (Analytica Chimica Acta, 2026)

A dual-mode colorimetric and electrochemical strategy for sensitive detection of PRRSV using imidazole-copper nanozymes - Jing Li; Xiang Lai; Chong Zhang; Yu-Fan Huang; Guo-Bao Ning; Si-Ying Ma; Ao-Xiang Chen; Ming-Rui Li; Guo-Hao Li; Qin Zhao; Can-Peng Li; Hui Zhao (Analytica Chimica Acta, 2026)

Associations of Paternal Seminal Plasma Metals with their Spouses’ Unexplained Recurrent Spontaneous Abortion (URSA) Risk and the Potential Mediating Role of Oxidative Stress - Hanyan Xi; Rui Yang; Huaqiong Bao; Huiru Li; Youzhu Li; Francis L. Martin; Wei Chen; Liang Chen; Yan Sun; Yan-Yang Lu; Qingyu Huang; Meiping Tian (Biological Trace Element Research, 2025)

Improved PSO-VMD seismic signal denoising method combined with modified wavelet transform - Hui Sun; Hong-yong Ren; Rui Chen; Xing-guo Huang; Wei Zhang; Yan-song Li; Jian Zhang; Yu-bo Yue (Applied Geophysics, 2025)

Dynamic response and liquefaction mitigation of immersed tunnels under seismic loads: A coupled seawater-seabed-tunnel analysis - Weiyun Chen; Zhiqiang Luo; Lingyu Xu; Yewei Zheng; Lei Su; Rui Huang (Soil Dynamics and Earthquake Engineering, 2025)

Interaction of secreted protein PgSLP and citrus calmodulin-like protein CsCML27/44 in fruit disease defense - Yao Xu; Ou Chen; Rong Zhu; Rui Huang; Jian Ming; Shixiang Yao; Kaifang Zeng (Postharvest Biology and Technology, 2025)

Arrangement optimization of wingsails subject to complex mutual aerodynamic interference: A numerical study - Ranqi Ma; Daize Li; Rui Zhang; Feng Tian; Zhiqiang Tang; Jianlin Cao; Yuhao Xie; Zihan Jing; Jijun Chen; Xiaowu Li; Lianzhong Huang (Ocean Engineering, 2025)

Resilient polyurea barriers for copper smelting wastewater containment: Synergistic effects of microstructural optimization and heavy metal immobilization - Feng Chen; Linhai Ye; Wenchang Li; Rui Xiang; Youcai Zhao; Qifei Huang; Ya Xu (Journal of Cleaner Production, 2025)

Indian summer monsoon variability across the last 9000 years: New evidence from stalagmites of southwestern China - Yanzhen Li; Chunju Huang; Jianghu Lan; David B. Kemp; James G. Ogg; Ashish Sinha; Lvfan Chen; Xiqian Wang; Huiru Tang; Xu Lin; Khalaf H.M. Abdel-Raheem; Rui Zhang; et al. (Global and Planetary Change, 2025)

Effects of cold plasma treatment and xanthan gum on the longan seed starch: physicochemical, rheological and digestive properties - Rui Huang; Yitong Chen; Lingfeng Cheng; Mengzhu Shen; Yaqin Yu; Fangfang Wu; Miaomiao Shi; Yong Hu; Chao Huang; Yun Chen (Food Chemistry, 2025)

Preparation and characterization of Ag@MOF-Amomum tsaoko essential oil/waterborne polyurethane composite films for strawberry preservation - Yuyue Qin; Hongda Yu; Haiyan Chen; Yongliang Zhuang; Qiuming Liu; Rui Cui; Cong Zhang; Charles Brennan; Yuanxiang Huang (Food Control, 2025)

Self-assembling metal–polyphenol–protein nanocomplex enhancing islet graft survival and transplantation outcome - Zeqing Wang; Yixuan Zhu; Huixiang Sheng; Yang Cheng; Ying Zhang; Yifei Yang; Zhuoxun Huang; Xiaoyue Chen; Yifan Qiu; Rui Wu; Di Huang; Wenjing Gong; et al. (Chemical Engineering Journal, 2025)

Defect-mediated dual role interfaces enables the sulfur reduction reaction kinetics for highly stable lithium sulfur batteries - Xinmeng Li; Jiafeng Zhu; Rui Sheng; Tianmei Xu; Kai Chen; Juan Ding; Yudai Huang (Chemical Engineering Journal, 2025)

Correction: Combining network Pharmacology and metabonomics to explore the mechanism of baicalin inhibiting PRRSV replication - Qin Luo; Yu-xuan Huang; Hai-rui Li; Chang-hong Qiao; Zhen-wen He; Xiang-yu Chen; Xiao-hu Wang; Gang Wang; Meng-meng Zhao; Ru-jian Cai (Veterinary Research Communications, 2025)

Combining network pharmacology and metabonomics to explore the mechanism of baicalin inhibiting PRRSV replication - Qin Luo; Yu-xuan Huang; Hai-rui Li; Chang-hong Qiao; Zhen-wen He; Xiang-yu Chen; Xiao-hu Wang; Gang Wang; Meng-meng Zhao; Ru-jian Cai (Veterinary Research Communications, 2025)

Theasinensin A: Formation, preparation, and bioactivities of a promising functional polyphenol in tea - Yiang Chen; Juan Wang; Yuexin Liu; Fuqing Bai; Jiali Yang; Rui Shi; Huimei Cai; Zhongwen Xie; Daxiang Li; Yujie Huang; Guijie Chen (Trends in Food Science & Technology, 2025)

Impacts of different types of wastewater discharge on plankton community structure in the receiving rivers of the Yangtze River - Rui Bian; Shier Huang; Xiaofeng Cao; Weixiao Qi; Jianfeng Peng; Huijuan Liu; Min Chen; Yufeng Chen; Jiuhui Qu (Environmental Pollution, 2025)

Photothermal modulation of the regenerative microenvironment for reversing optic nerve injury - Kexin Tan; Jiayu Wang; Qianyue Zhang; Shuo Wu; Haiyang Zhang; Yusha Liu; Zhaohan Qu; Siwei Liu; Rui Huang; Yan Liu; Yang Wang; Yingzhi Chen; et al. (Chemical Engineering Journal, 2025)

Interfacial engineering of 0D/3D CeO2/BA nanoarchitectures for highly efficient and selective CO2 photo-reduction to CH4 based on full-spectrum solar-energy utilization - Rui Xu; Chonghai Deng; Chengchen Wang; Yibin Zhu; Yonghui Tong; Zheng Chen; Peipei Sun; LiLi Wang; Lei Yang; Xin Liang; Yiping Wu; Jing Huang; et al. (Chemical Engineering Journal, 2025)

Dual-catalytic polymerization of high-performance PEDOT thermoelectric fabrics for self-powered sensing - Yifan Cui; Qin Chen; Wuwei Bao; Hao Yao; Zhenzhe Huang; Rui Ma; Miao Miao; Lizhi Sheng; Xinyang He (Chemical Engineering Journal, 2025)

Cinnamaldehyde enhanced starch/chitosan composite films: A one-pot engineered solution for extended fruit shelf life - Qingbo Yao; Yan Chen; Zhizhi Zhang; Weijian Chen; Rui Wang; Langhong Wang; Yanyan Huang; Fengsong Liu; Xin-An Zeng (Carbohydrate Polymers, 2025)

Hydrological processes in continental valley basins: evidence from water stable isotopes - Rui Li; Xiaoyu Qi; Longhu Chen; Guofeng Zhu; Gaojia Meng; Yuhao Wang; Enwei Huang; Yinying Jiao; Qinqin Wang; Wenmin Li (CATENA, 2025)

Vertical distribution, optical properties, and source attribution of summer dust in southern Tajikistan: ground-based observations and model results - Zhongwei Huang; Qingqing Dong; Tian Zhou; Jianrong Bi; Rui Chen; Qiantao Liu; Sabur F. Abdullaev; Dilovar Nozirov; Khan Alam; Tianhe Wang; Wuren Li; Ze Li; et al. (Atmospheric Environment, 2025)

Mechanism of endoplasmic reticulum stress-induced endothelial cell ferroptosis in trichloroethylene-induced mouse kidney injury - Meng Huang; Jiaxiang Zhang; Rui Li; Jian Chen; Qixing Zhu; Haibo Xie (Toxicological Research, 2025)

Identification of a hypoxia-related gene signature associated with childhood asthma - Wenlie Chen; Yuanlu Huang; Li Lei; Rui Zhang; Li Fu; Jinwen Liao; Shaohua Wang; Zhenzhuang Zou (Genes & Genomics, 2025)

A copper-based single-atom material effectively controls plant diseases with nearly zero soil residue and low phytotoxicity - Rui Huang; Yong Yan; Yafei Jiang; Chunyan Gu; Zhentao Ma; Lifang Xue; Yao Ma; Xingen Lin; Juan Zhang; Ran Shi; Yiwen Wang; Linjing Liu; et al. (Science Bulletin, 2025)

Fossil involucres and a nutlet of Ostrya (Betulaceae) from the upper Eocene of Shaanxi and their biogeographic implications - Jiao Huang; Hui Jia; Rui-Feng Yan; Xiang-Ning Meng; Zhuo-Chen Han; Tian-Qi Dong; Jian Pan; Cheng Quan (Palaeoworld, 2025)

Introducing street view into node-place model for evaluating transit-oriented development - Jiayu Liu; Xiping Yang; Xiaoyan Huang; Jiyuan Li; Junyi Li; Hongfei Chen; Rui An; Yongyong Song (Journal of Transport Geography, 2025)

Efficient degradation of dichloromethane by novel cell-immobilized-filled biotrickling filters: Performance and mechanisms - Yaxue He; Xiaoyan Li; Rui Han; Aohan Zhang; Ya Deng; Piet N.L. Lens; Christian Kennes; Zhao Huang; Jianmeng Chen; Guangfeng Yang; Dongzhi Chen (Journal of Hazardous Materials, 2025)

Mechanisms of cypermethrin degradation and remediation by Rhodococcus sp. H-3: Insights from comparative genomics, hydrolase CymE1 secretory expression, and bacterial community analysis - Guoqiang Zhao; Wenjing Chen; Rongrong Zhang; Rui Zhang; Bo Jiang; Ruyan Hou; Xing Huang (Journal of Hazardous Materials, 2025)

Changes and responses of GPP among different plant functional types in a savanna ecosystem under future climate scenarios - Weiduo Chen; Xuehai Fei; Jingyu Zhu; Rui Chen; Haiqiang Du; Yingqian Huang; Yong Zhang; Yi Shen; Aping Niu; Peng Xu (Journal of Environmental Management, 2025)

Benzotriazole (BT) and benzothiazole (BTH) derivatives as emerging marine pollutants in the Pearl River Estuary: Spatiotemporal distribution, environmental fates, and ecological risks - Xiaoxiao Chen; Qianyi Huang; Rui Hou; Shan Liu; Hengxiang Li; Tiantian Chen; Xiangrong Xu (Environmental Pollution, 2025)

Bioinspired conductive-catalytic network accelerates rate-determining steps at cathode-electrolyte interface for high-loading Li-S batteries - Cai-Yun Zhang; Chen-Yang Wang; En-Zhu Zhao; Guowei Yu; Hui-Ling Deng; Rui Huang; Zhao-Yun Wang; Pu Hu; Min Yan; Zhitian Liu (Chemical Engineering Journal, 2025)

Self-healing sodium alginate-PEDOT:PSS conductive hydrogel for accelerated burn wound healing and real-time monitoring - Xinshuo Liu; Feng Chen; Yifan Zhang; Zexiang Zheng; Rui Huang; Jinhuan Tian; Hong Li; Changren Zhou; Shuyun Zhang; Huihua Xu; Lihua Li (Chemical Engineering Journal, 2025)

Multifunctional flexible multilayer pressure sensor for pressure sensing, energy harvesting and versatile applications - Fu-Rui Teng; Song Sun; Si-Chen Tan; Ying-Jie Ma; Yue Huang; Lin Zhu; Di Wu; Ai-Dong Li (Chemical Engineering Journal, 2025)

Vapor additive strategy enabling perfect crystallization of vacuum-evaporated photovoltaic perovskites - Lei Huang; Zhang Chen; Kai-Li Wang; Zi-Hao Song; Xiao-Ying He; Zhen-Huang Su; Jing Chen; Chun-Hao Chen; Yu Xia; Yu-Tong Yang; Xin Chen; Rui-Hao Qin; et al. (Chemical Engineering Journal, 2025)

A 3D-printed chitosan-based pH-responsive dual functional scaffold for osteomyelitis: synergistic antibacterial and osteogenic treatment - Mingyue Lin; Yijing Stehle; Li Chen; Mao Yang; Ke Zeng; Chenxin Wang; Rui Zhang; Huanshuo Zhang; Jiehui Yang; Denglang Hu; Min Huang; Yubao Li; et al. (Carbohydrate Polymers, 2025)

Effect of primate protection on threatened and endemic vertebrates, plants, ecosystem services, and future climate refugia - Yin Yang; Chen Li; Yi‐Hao Fang; Guo‐Peng Ren; Zhi‐Pang Huang; Yan‐Peng Li; Liang‐Wei Cui; Meng‐Ran Chu‐yuan; Colin A. Chapmman; Cyril C. Grueter; Jian Zhou; Wen‐Bo Yan; et al. (Conservation Biology, 2025)
Primates, 69% of which are threatened with extinction, are the third most specious order of mammals. We used primates as model taxa to examine the umbrella effects of primates on ecosystem services and the protection of other vertebrates and seed plants in Yunnan Province, China. We identified areas of conservation priority for 16 primate species and determined which other threatened and endemic terrestrial vertebrates and seed plants would be protected through a program targeting primate conservation. Areas of high primate species richness were spatially correlated with the distribution of 601 species of threatened and endemic vertebrates and 4010 seed plants. Primate species richness was positively correlated with carbon sequestration and enhanced water and soil conservation and coincided with future areas of climate refugia. If 30% of Yunnan's land area were designated as primate conservation priority areas, then 52.3% of the province's average annual carbon sequestration, 51.7% of its water conservation, 54.1% of its soil retention, and 30‐33% of its climate‐stable areas would be protected. Protecting primates as umbrella taxa uniquely contributes to maintaining biodiversity and ecosystem services that promote ecosystem stability. Although we focused on a single mammalian order in a single region, our approach for umbrella taxa evaluation has broad applicability and can help achieve multiple conservation targets of the Kunming–Montreal Global Biodiversity Framework.

YOLO-feed: An advanced lightweight network enabling real-time, high-precision detection of feed pellets on CPU devices and its applications in quantifying individual fish feed intake - Miaosheng Feng; Pengxin Jiang; Yuhang Wang; Shuimu Hu; Sijing Chen; Rui Li; Haibin Huang; Ning Li; Boyu Zhang; Qiaozhen Ke; Yu Zhang; Peng Xu (Aquaculture, 2025)

Unveiling city-scale urban roadside charging piles capacity: Geospatial knowledge-assisted small object detection and SDG 7-driven planning - Qin Huang; Teng Zhong; Liangchen Zhou; Rui Zhu; Xiao Fu; Changchang Zhou; Min Chen; Guonian Lü (Sustainable Cities and Society, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Associations Between Pre- and Post-Diagnosis Dietary Inflammatory Patterns and Ovarian Cancer Survival: Results From the Ovarian Cancer Follow-Up Study - Jia-Xin Liu; Rui-Han Bao; Meng Luan; Chuan Liu; Lang Wu; Fang-Hua Liu; Yi-Zi Li; He-Li Xu; Yi-Fan Wei; Qian Xiao; Dong-Hui Huang; Xiao-Ying Li; et al. (Journal of the Academy of Nutrition and Dietetics, 2025)

Microplastics impair black soldier fly bioconversion of pigeon manure: Physiological and transcriptomic insights - Zhimin Xu; Zheng Lin; Runtong Huang; Xueqing Chen; Lei Wang; Xingying Deng; Rui Du; Jiguang Gu; Yifan Wang; Renqiang Yu (International Biodeterioration & Biodegradation, 2025)

Deep-sea rare earth element-rich sediments: A review of distribution, carriers and petrogenesis - Yu Fu; Zhengkun Li; David Chew; Pete Hollings; Jinzhou Peng; Jieyun Chen; Bojue Tan; Gaowen He; Yongjia Liang; Fei Huang; Yayue Tang; Rui Wang; et al. (Global and Planetary Change, 2025)

Catalytic dehydrogenation of propane by electrospinning one-dimensional Zn-Ga2O3-Al2O3 nanofibres under CO2 atmosphere - Rui Chen; Xue Han; Yixuan Yang; Xupeng Yang; Yuqi Wang; Yupeng Zhang; Tiange Huang; Jie Wei; Junjie Ding; Xuyu Wang; Hongbing Ji (Fuel, 2025)

Sterigmatocystin in rice through LC-MS/MS: Longitudinal study on contamination, health risks and residual patterns in China - Yarong Zhao; Lan Wang; Rui Zeng; Peirong Chen; Kaihang Xu; Xiaomei Huang; Aibo Wu (Food Chemistry, 2025)

An ultrasound-visualized methionine partitioning nano-modulator for enhanced immunotherapy against anti-PD-1 resistant tumors - Yingying Zhao; Beibei Zhang; Shaobo Duan; Yaqiong Li; Yuzhou Wang; Yongchao Wang; Juan Zhang; Rong Huang; Ru Jiang; Rui Zhang; Qi Zhou; Linlin Zhang; et al. (Chemical Engineering Journal, 2025)

Oral HMPB/Mn3O4 nanozymes for the treatment of ulcerative colitis via cellular redox balance regulation, gut microbiota modulation, and ferroptosis inhibition - Han Wang; Yexin Liu; Rui Huang; Weirui Chen; Luxuan Chen; Huacai Shi; Si Lei; Qi He; Ri Chen; Lihua Zhou; Wenxia Wang; Yanling She (Chemical Engineering Journal, 2025)

Endothelial Cell Integrin α6 Regulates Vascular Remodeling Through the PI3K/Akt-eNOS-VEGFA Axis After Stroke - Bing-Qiao Wang; Yang-Ying Duan; Mao Chen; Yu-Fan Ma; Ru Chen; Cheng Huang; Fei Gao; Rui Xu; Chun-Mei Duan (Neuroscience Bulletin, 2025)

Effect of Drought Stress on Root Metabolome and Soil Microbial Characteristics for Maize (Zea mays L.) Seedlings - Rui Hao; Hao Li; Shufang Qin; Wenquan Chen; Qiuchen Guo; Yanan Huang; Xiaohong Chen; Yajun Li (Current Microbiology, 2025)

Effect of human-driven hydrological change on vegetation distribution in the Shiyang River Basin - Yuhao Wang; Guofeng Zhu; Enwei Huang; Gaojia Meng; Jiawei Liu; Siyu Lu; Dongdong Qiu; Longhu Chen; Rui Li; Yinying Jiao; Ling Zhao; Xiaoyu Qi; et al. (Journal of Mountain Science, 2025)

A SERS aptasensor based on Au@Ag bimetallic nanostars-magnetic covalent organic composites for rHuEPO-α detection - Na Zhou; Yu Zeng; Qiuwen Huang; Rui Tan; Yushi Chen; Liu Zhong; Xiaojun Luo; Xiaojun Deng (Analytica Chimica Acta, 2025)

One-billion-year-old eukaryotic algal fossil Arctacellularia from North China and its implications for the evolution of pre-Cryogenian filamentous multicellularity - Rui Huang; Guangjin Li; Jiayue Wang; Qing Tang; Mingyang Qiu; Qian Chen; Hanzhi Qu; Chengxi Wu; Wenfei Cui; Xianqin Yan; Chuanming Zhou; Xunlai Yuan; et al. (Precambrian Research, 2025)

A framework for spatial correlations between industrial pollution sources and groundwater vulnerabilities based on machine learning and spatial cluster analysis: Implications for risk control - Rui Zhou; Jian Chen; Haobo Bian; Lu Li; Tao Zhang; Lei Liao; Haobo Niu; Leyi Yin; Guoxin Huang (Journal of Hazardous Materials, 2025)

Soil-dependent responses of bacterial communities, phosphorus and carbon turnover to uranium stress in different soil ecosystems - Huang Yu; Dandan Zhang; Rui Xiong; Shengwei Liu; Ruiwen Hu; Pubo Chen; Xiaoyan Wu; Hantong Zou; Nan Hu; Dexin Ding; Qingyun Yan; Zhili He (Journal of Hazardous Materials, 2025)

Palmitic acid triggers rhizosphere acidification to facilitate microbial nitrogen fixation: A perspective for phytoremediation of desertification alpine grassland via artificial root exudation mimicking - Fei Yan; Qian Huang; Dongming Chen; Xin Zheng; Rui Yin; Kangqi Zhang; Yan Lu; Yanfu Bai; Feida Sun; Jiqiong Zhou; Zhouwen Ma; Geng Sun; et al. (Journal of Environmental Management, 2025)

A method on the induction of piezoelectricity of PVDF by NaOH: Induced PVDF as ultrafiltration base membrane in interfacial polymerization to enhance the rejection of NaCl - Yuliang Chen; Wenmin Wang; Ying Liang; Chen Chen; Rui Meng; Libo Ba; Yuliang Wu; Yijiang Liu; Weiwei Huang; Fei Yang; Jun Cheng; Xuesong Yi (Desalination, 2025)

Preparation of polyester amide nanofiltration membrane by low concentration hydroxyl monomer induced piperazine through intermolecular interaction - Yuliang Wu; Rui Meng; Chen Chen; Yuliang Chen; Libo Ba; Yijiang Liu; Weiwei Huang; Fei Yang; Jun Cheng; Xuesong Yi; Shitao Zhi; Yajie Pang (Desalination, 2025)

Females adapted better than males in Populus deltoides to simulated nitrogen deposition - Fang He; Shu-Ying Wei; Rui-Quan Wang; Jia Yao Tang; Peng Yang; Ting Wang; Jin-Liang Huang; Gang Chen; Tian-Tian Lin (Plant and Soil, 2025)

Revealing the Oxidative Stress-Related Molecular Characteristics and Potential Therapeutic Targets of Schizophrenia through Integrated Gene Expression Data Analysis - Xiu-Mei Zhu; Ji Chen; Hua-Jie Ba; Chun Yang; Jian-Wei Liu; Rui Guo; Shi-Lin Li; Ping Huang; Cheng-Tao Li; Su-Hua Zhang (Molecular Neurobiology, 2025)

Ferritinophagy-derived iron causes protein nitration and mitochondrial dysfunction in acetaminophen-induced liver injury - Shi-Min Liang; Jie Shen; Rui-Ting Ma; Nan-Di Du; Rui Wang; Zuo-Min Wu; Min Shan; Shi-Rong Liang; Wei-Rong Hu; Wei Wang; Wei-Wei Sheng; De-Feng Huang; et al. (Toxicology and Applied Pharmacology, 2025)

Adaptive online modeling of ship maneuvering based on multiscale convolutional hybrid SRU models - Haoyang Zhao; Lianzhong Huang; Ranqi Ma; Kai Wang; Jianlin Cao; Tiancheng Wang; Zhang Ruan; Rui Zhang; Yingbo Zang; Weiping Li; Xiangjun Chen (Ocean Engineering, 2025)

Anti-fouling array paper-based device for rapid and accurate discrimination of foodborne pathogens in real samples - Kuiyu Wang; Yayue Huang; Yu Wan; Wang Chen; Jianwei Liang; Liangke Gong; Zebao Rui; Tao Yang (Food Chemistry, 2025)

Effect of annealing and tea polyphenols on the physicochemical properties of mango starch - Rui Huang; Yaqin Yu; Mengzhu Shen; Lingfeng Cheng; Yitong Chen; Hongwei Wu; Fangfang Wu; Chao Huang; Yong Hu; Yun Chen (Food Bioscience, 2025)

A novel bioreactor developed for the intensification of high-viscosity aerobic fermentation processes - Qian Chen; Kai Hu; Quanfei Li; Kai Yang; Chao Zhang; Weiwei Huang; Yibin Qiu; Yian Gu; Liang Sun; Peng Lei; Jian Xue; Sha Li; et al. (Chemical Engineering Journal, 2025)

Fire ant-inspired bone repair breakthrough: Self-assembly strategy of microspheres driven by physical hydrogen bonding and hydrophobic interactions - Rui Zhang; Yijing Stehle; Li Chen; Ke Zeng; Mingyue Lin; Chenxin Wang; Huanshuo Zhang; Jiehui Yang; Denglang Hu; Min Huang; Mao Yang; Yubao Li; et al. (Chemical Engineering Journal, 2025)

One-step forming strategy of highly stable Li4SiO4 for low-concentration CO2 capture - Yu Zhang; Shuo Chen; Shikun Wen; Jiaojiao Li; Rui Yang; Liang Huang; Junya Wang; Ping Ning; Qiang Wang (Chemical Engineering Journal, 2025)

A novel approach to healthy water Treatment: Boiling-Based UV photoelectrochemical oxidation process for the removal of disinfection by-products from drinking water - Xingxing Huang; Yujie Ao; Haocheng Yang; Muyu Feng; Xuan Wang; Rui Chen; Qing Yang; Jinsuo Lu (Chemical Engineering Journal, 2025)

The effect of soil microbial functional groups, abiotic and biotic factors on plant functional groups: insights from a tropical rainforest in Southwest China - Yanxuan Chen; Xiaobo Huang; Rong Tang; Rui Zhang; Cong Li; Tongli Wang; Jianrong Su; Shuaifeng Li (Plant and Soil, 2025)

Linking gut microbiome profiles and white matter integrity to social behavior in young autistic children: from the perspective of individual variation - Xinyue Huang; Weixing Zhao; Rui Feng; Yuanyue Zhou; Jia Wang; Jinming Xiao; Lei Li; Xiaolong Shan; Yu Feng; Yating Ming; Jing Cao; Xiaodong Kang; et al. (Science Bulletin, 2025)

The long noncoding RNA VIVIpary promotes seed dormancy release and pre-harvest sprouting through chromatin remodeling in rice - Lu Yang; Yu Cheng; Chao Yuan; Yan-Fei Zhou; Qiao-Juan Huang; Wen-Long Zhao; Rui-Rui He; Jie Jiang; Yi-Chao Qin; Zheng-Tong Chen; Yu-Chan Zhang; Meng-Qi Lei; et al. (Molecular Plant, 2025)

Mechanism of quartz flotation separation from gypsum using tetradecyl trimethyl ammonium chloride: Guiding the improvement of phosphogypsum quality - Haodong Shi; Liuyi Ren; Shenxu Bao; Yimin Zhang; Anh V. Nguyen; Bo Chen; Weifeng Li; Rui Huang; Yanqi Zeng; Sidi Lou (Minerals Engineering, 2025)

Comparative mechanisms of PDS-activated antibiotic remediation in groundwater via controlled-release materials with different mesoporous catalysts - Ting Wang; Jing-le Chen; Rui Huang; Hua-li Chen; Cheng Hu; Gang Chen; Kou-ping Chen; Ji-chun Wu (Journal of Environmental Management, 2025)

Unveiling the hidden environmental risk of biochar: Take colony-forming Microcystis as biotoxicological indicator - Jiang Huang; Xiao Tan; Zhipeng Duan; Jia Liang; Rui Zhu; Shichao Chen (Journal of Environmental Chemical Engineering, 2025)

Oriented conversion of low-value heavy oil to acetylene and hydrogen using pulsed spark discharge - Hang Wang; Rui Wu; Liguang Dou; Dengke Xi; Bangdou Huang; Zhuofei Wang; Shuai Zhang; Zhe Fan; Shuai Yang; Cheng Zhang; Guoxing Chen; Tao Shao (Chemical Engineering Journal, 2025)

Identification of Age-Related Characteristic Genes Involved in Severe COVID-19 Infection Among Elderly Patients Using Machine Learning and Immune Cell Infiltration Analysis - Huan Li; Jin Zhao; Yan Xing; Jia Chen; Ziying Wen; Rui Ma; Fengxia Han; Boyong Huang; Hao Wang; Cui Li; Yang Chen; Xiaoxuan Ning (Biochemical Genetics, 2025)

Ecological security and structural optimization of land space in the Pearl River Delta Urban Agglomeration: an approach based on the footprint family - Cong Huang; Jun Liu; Hanyu Yin; Zhonghao Zhang; Wei Cao; Wenfang Tan; Xufeng Fei; Chen Xu; Lumeng Liu; Jiali Chen; Kai Li; Rui Xiao (Environment, Development and Sustainability, 2025)

Analytical investigation of free vibration analysis in functionally graded graphene platelet-reinforced composite beams - Rui Ma; Chen Huang; Lei Cao; Yong Cao; Tianchen Zhao; Jianqiang Zhou; Chao Zhang (Wave Motion, 2025)

The antioxidant protein PntA coordinates with OmpW to resist oxidant stress in Actinobacillus pleuropneumoniae - Weiyao Han; Qiuhong Zhang; Zhen Luo; Hao Tang; Xiabing Chen; Qi Huang; Rui Zhou; Lu Li (Veterinary Microbiology, 2025)

Exposure routes induce differential intestinal damage in zebrafish from polystyrene microplastics - Zhenhua Yan; Yuqiong Yang; Jing Xiang; Yufang Chen; Peiyuan Zhu; Saiyu Yuan; Rui Huang; Xiaodong Hu; Yiming Ma (Process Safety and Environmental Protection, 2025)

The Quanjishan Charnia assemblage from the northern Qaidam Basin, Tibetan Plateau, and implications for palaeoecology and taphonomy of Ediacaran fronds - Chengxi Wu; Alexander G. Liu; Yarong Liu; Xiaopeng Wang; Guangjin Li; Hanzhi Qu; Rui Huang; Mingyang Qiu; Wentao Zheng; Yunpeng Sun; Hongyi Shi; Qing Ouyang; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Graphene irradiation heating on corn grains: Effects on bioactive compounds, thermal, structural, and functional properties of corn flour - Abdulaziz Nuhu Jibril; Jiang Zheng; Rui Zhu; Mustapha Muhammad Nasiru; Ambika Paswan; Jichao Huang; Kunjie Chen (Journal of Cereal Science, 2025)

Impact of the drying process on the flavor characteristics of two economically important laver species, Pyropia haitanensis and Neopyropia yezoensis - Yuting Zhang; Juanjuan Chen; Yongbo Huang; Qijun Luo; Rui Yang; Peng Zhang; Tiegan Wang; Haimin Chen (Food Chemistry, 2025)

Increased spike density and enhanced vegetative growth as primary contributors to improvement of dryland wheat yield via surface mulching - Yuwei Chai; Yawei Li; Rui Li; Lei Chang; Hongbo Cheng; Jiantao Ma; Yuqing Qin; Fanxiang Han; Changgang Yang; Yuzhang Chen; Qian Chen; Yao Zhang; et al. (Field Crops Research, 2025)

The application of marine bioactive composite materials in environmental remediation - Yanan Huang; Hao Li; Ronglian Xing; Xiaorui Chen; Yuxin Sun; Meichen Tian; Ran Zhang; Xin Wang; Xinxin Wang; Rui Li; Lihong Chen; Hongxia Zhang; et al. (Desalination, 2025)

Constructing a dual-layer PTFE nanofiltration membrane for enhanced salt solution permeability - Fuxin Qiu; Fan Liu; Rui Tian; Xutong Han; Kaikai Chen; Qinglin Huang (Desalination, 2025)

A new insight into the transformation mechanism between reactivity of aqueous monomer and chlorine resistance of polyester-amide nanofiltration membrane - Yuliang Wu; Rui Meng; Chen Chen; Yuliang Chen; Libo Ba; Yijiang Liu; Weiwei Huang; Fei Yang; Yanshan Wang; Jun Cheng; Xuesong Yi; Heng Liang (Desalination, 2025)

Cation-induced phase transformation in PVDF for efficient energy harvesting - Dinku Hazarika; Jiaqi Lu; Jiafeng Ni; Chuanrui Chen; Muhammad Naeem Shah; Liangquan Xu; Jianhui Wu; Kaihang Zhang; Jie Li; Xinyu Cai; Rui Wan; Hao Jin; et al. (Chemical Engineering Journal, 2025)

Histone H3K36 methyltransferases NSD1 and SETD2 are required for brain development - Bo Chen; Chenyang Zhang; Huanwen Rui; Dan Shen; Zhuxi Huang; Weijun Feng (Human Genetics, 2025)

Unsteady hydrodynamic characteristics control of turbine blades by the vortex generators - Guotao Jia; Cong Chen; Lu Wang; Pengzhong Wang; Bin Huang; Rui Wu (Ocean Engineering, 2025)

ANAC050 confers aluminium resistance by cooperating with secretion of organic acids and accumulation of cell wall hemicelluloses in plants - Ye TAO; Su LI; Yusong LIU; Rui GUO; Changzhao CHEN; Jiu HUANG; Qiang ZHANG; Renfang SHEN; Xiaofang ZHU (Pedosphere, 2025)

Graph-based pangenome provides insights into structural variations and genetic basis of metabolic traits in potato - Xiaoling Zhu; Rui Yang; Qiqi Liang; Yuye Yu; Tingting Wang; Li Meng; Ping Wang; Shaoyang Wang; Xianping Li; Qiongfen Yang; Huachun Guo; Qijun Sui; et al. (Molecular Plant, 2025)

A comprehensive review on selenium and blood pressure: Recent advances and research perspectives - Pusong Tang; Rui Huang; Xing Zhong; Xin Chen; Yuhua Lei (Journal of Trace Elements in Medicine and Biology, 2025)

Enhanced effects and mechanisms of Tween80 on aniline biodegradation by newly isolated Pseudomonas veronii T1 - Yufeng Fu; Tingdi Zhang; Chuanyu Qin; Chengwu Zhang; Jintao Ru; Rui Tang; Guoxin Huang; Jian Chen (Journal of Environmental Chemical Engineering, 2025)

Selective preparation of aromatic compounds from catalytic pyrolysis polyester coating over Ni, Mo and Co metal modified ZSM-5 - Zhen-Qiang Yu; Yao-Xin Xiao; Dong Liang; Che Zhao; Zhen Huang; Gang-Qi Cheng; Rui Shan; Hao-Ran Yuan; Yong Chen (Journal of Environmental Chemical Engineering, 2025)

NIR-activated endoplasmic reticulum stress amplifier to regulate phagocytosis for macrophage-mediated cancer immunotherapy - Yaru Zhang; Wenyu Xie; Jiamin Luo; Rui Gao; Zhimin Gao; Xinyi Wang; Yongxin Huang; Chen Lin; Meiling Tan; Zhiyao Hou (Chemical Engineering Journal, 2025)

Heavy metal and metalloid source identification in lake and river sediment in the Honghu Watershed: Coupling land use analysis with RDA and PMF in central China - Yuanzheng Liu; Xiaoguo Chen; Xi Liu; Cong Wang; Lu Zhang; Rui Zhou; Zhi Wang; Xiaolong Huang (Journal of Soils and Sediments, 2025)

Monsoon Climate and Anthropogenic Influences Shape Primate Distributions Across the Southeastern Edge of the Qinghai‐Tibet Plateau - Chen Li; Yi‐hao Fang; Guo‐peng Ren; Yan‐peng Li; Zhi‐pang Huang; Liang‐wei Cui; Dionisios Youlatos; Paul A. Garber; Xi‐jun Ni; Hua Zhu; De‐wen Luo; Xin Liu; et al. (Global Change Biology, 2025)
The southeastern edge of the Qinghai‐Tibet Plateau (Yunnan, China) exhibits high biodiversity but stark differences in species richness between its western Longitudinal Range Gorge (LRG) and eastern Yunnan Plateau (YP). We collected distribution data for 16 primate species in Yunnan and analyzed palynological records over the past 20 ka from 21 localities to identify the biogeographic, climatic, and anthropogenic factors that have driven the present‐day distribution of primates in this region. By integrating local ecological knowledge, field surveys, species distribution models, niche utilization rates, and historical vegetation and land use changes, we found that spatial–temporal shifts in the monsoon climate have been a critical factor in shaping primate species richness on the southeastern edge of the Qinghai‐Tibet Plateau. Compared to the YP, the LRG receives more precipitation, has more limited seasonal temperature variation, and has higher minimum temperatures during the coldest month. These conditions have facilitated the development of moist evergreen broadleaf forests, which represent a more suitable habitat for the 14 primate species that inhabit this area. In contrast, the drought‐adapted forests of the YP support only one primate species. Palynological records indicate that the differentiation of the LRG and YP predates human influence. However, over the past 2000 years, anthropogenic habitat loss and hunting have significantly affected the distribution of primates. The ranges of gibbons, langurs, and snub‐nosed monkeys are now restricted to the central and northern regions of the LRG and have disappeared from lower elevations. Lorises have disappeared from their northernmost range. In contrast, the distribution of macaques has remained relatively stable. The Yangtze‐Red River‐24° N line marks the biogeographic boundary of high primate species richness and biodiversity in the LRG and southeastern Yunnan. Our research suggests that changes in monsoon climate have fundamentally shaped contemporary species richness, while recent anthropogenic pressures have caused ‘range contraction’ for many taxa.

Transcriptome profiling in peanut (Arachis hypogaea) in response to biotic stress produce by Bacillus amyloliquefaciens TA-1 - Wang Chen; Taswar Ahsan; Di Han; Wen-Rui Wang; Si-Tong Du; Chao-Qun Zang; Yu-Qian Huang; Ejaz Hussain Siddiqi (Plant Gene, 2025)

Soil organic carbon dynamics (2008–2020) across different cultivated land use types in a subtropical region - Jianming Li; Siqi Li; Rui Zhao; Shihe Xing; Hanyue Chen; Yan Huang; Liming Zhang; Jing Li (Geoderma Regional, 2025)

Fruit wines classification enabled by combing machine learning with comprehensive volatiles profiles of GC-TOF/MS and GC-IMS - Changlin Zhou; Yashu Yu; Jingya Ai; Chuan Song; Zhiyong Cui; Quanlong Zhou; Shilong Zhao; Rui Huang; Zonghua Ao; Bowen Peng; Panpan Chen; Xiaoxiao Feng; et al. (Food Research International, 2025)

Spectral analysis of the impact of various polysaccharides on the entrapment of curcumin by whey protein isolate - Yuhan Yan; Rui Tang; Feng Li; Liurong Huang; Yu Chen; Ronghai He (Food Chemistry, 2025)

Development of starch-based films with enhanced hydrophobicity and antimicrobial activity by incorporating alkyl ketene dimers and chitosan for mango preservation - Yanyan Huang; Qingbo Yao; Rui Wang; Langhong Wang; Jian Li; Boru Chen; Fengsong Liu; Xin-An Zeng (Food Chemistry, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Corrigendum to “Chargeable persistent luminescence 3D-printed scaffolds: A stepwise tactic for osteosarcoma treatment” [Chem. Eng. J. 479 (2024) 147436] - Rui Huang; Ni Ni; Yun Su; Li Gu; Yahan Ju; Dandan Zhang; Jipeng Li; Meiqi Chang; Yu Chen; Ping Gu; Xianqun Fan (Chemical Engineering Journal, 2025)

Dynamics of soil phosphorus fractions during the early recovery stage of two typical plantations in China after strip clearcutting - Linhui Zhang; Jihong Li; Su Chen; Wenlan Huang; Lulu Huang; Hongfeng Zhu; Yuanxiang Tang; Han Li; Chengming You; Lixia Wang; Sining Liu; Hongwei Xu; et al. (CATENA, 2025)

The Impact of Different Mating Systems on Locomotion in Drosophila melanogaster - Rui Han; Jun Zhang; Ruo-Xi Wang; Jia-Xin Xu; Kai-Chen Weng; An-Xin Wang; Hao Huang; Yu-Yuan Lu; Yi-Jie Chen; Yu-Chen Wang (Journal of Insect Behavior, 2025)

Cyclic peptides from cyanobacteria: Structural insights, biological functions, and mechanisms of cyclization - Nuo Chen; Rui Huang; Hangzhen Lan; Jouni Jokela; Huamao Wei; Shuai Zhi; Liwei Liu (Algal Research, 2025)

Global prevalence of lagomorpha coccidiosis from 1951 to 2024: A systematic review and meta-analysis - Huang-Liang Chen; Qi-Tao Zhang; Rui Qi (Research in Veterinary Science, 2025)

A data-driven framework to identify influencing factors for soil heavy metal contaminations using random forest and bivariate local Moran's I: A case study - Rui Zhou; Jian Chen; Shiwen Cui; Lu Li; Jiangbo Qian; Hang Zhao; Guoxin Huang (Journal of Environmental Management, 2025)

On using an aerosol thermodynamic model to calculate aerosol acidity of coarse particles - Zhengyang Fang; Shuwei Dong; Chengpeng Huang; Shiguo Jia; Fu Wang; Haoming Liu; He Meng; Lan Luo; Yizhu Chen; Huanhuan Zhang; Rui Li; Yujiao Zhu; et al. (Journal of Environmental Sciences, 2025)

Graphene bilayer film responsive to ultraviolet, humidity, and temperature - Lin Wang; Tao Wang; Yalong Li; Yi Huang; Rui Li; Jing Zhang; Jie Jiang; Pei Li; Yan Fan; Liang Chen (Chemical Engineering Journal, 2025)

A ferroptosis-targeting detachable dissolvable microneedle as a combined therapeutic strategy for radiation-induced oral mucositis - Yanxuan Xiao; Caiyong Song; Hongping Ye; Dan Li; Jiayi Shi; Xiaoke Huang; Qianming Chen; Rui Liu (Chemical Engineering Journal, 2025)

Factors governing bark tufa deposition in fluvial systems: the case study of Nuorilang in Jiuzhaigou, Sichuan China - JunHao Li; FuDong Wang; WuYang He; QinYingZi Cai; Shi Chen; GuoQing Huang; Dawood Muhammad; Carlos Pérez-Mejías; Rui Zhang; ZiTong Peng; SiRui Chen; ChenWei Ji; et al. (Carbonates and Evaporites, 2025)

Foxa1 disruption enhances human cell integration in human-mouse interspecies chimeras - Li-na Wang; Jun-shuang Jia; Xing-long Yang; Yue-ting Wen; Jing-xian Liu; Deng-ke Li; Xing-rui Chen; Jia-hong Wang; Ji-ke Li; Zhong-xi Huang; Kai-tai Yao (Cell and Tissue Research, 2025)

Microglia programmed cell death in neurodegenerative diseases and CNS injury - Ling Cai; Qiuyue Fan; Rui Pang; Chen Chen; Yueman Zhang; Haiyi Xie; Jingyi Huang; Yu Wang; Peiying Li; Dan Huang; Xia Jin; Yuxi Zhou; et al. (Apoptosis, 2025)

Toward safe rice production in As-Cd co-contaminated paddy soils: Biogeochemical mechanisms and remediation strategies - Jing-Min Yang; Hui-Lin Chen; Xin Wang; Dong-Xing Guan; Xiong-Hui Ji; Yun-He Xie; Rui Huang; Bo Peng; Qin-Bo Qin (Critical Reviews in Environmental Science and Technology, 2025)

Debaryomyces nepalensis enhances suberin deposition in citrus fruit wound by facilitating the synthesis of cinnamic acid and its derivatives - Jian Huang; Qi Chen; Ou Chen; Xiaoquan Gao; Rong Zhu; Rui Huang; Shixiang Yao; Lanhua Yi; Kaifang Zeng (Postharvest Biology and Technology, 2025)

Effects of cascade hydropower stations on hydrologic cycle in Xiying river basin, a runoff in Qilian mountain - Rui Li; Guofeng Zhu; Siyu Lu; Gaojia Meng; Longhu Chen; Yuhao Wang; Enwei Huang; Yinying Jiao; Qinqin Wang (Journal of Hydrology, 2025)

Influence of process parameters on the operation effectiveness of groundwater circulation well and multi-objective optimization design - Shaoyin Chen; Zixuan Huang; Rui Zhou (Journal of Environmental Management, 2025)

Human settlement and destructive activities disrupt the positive contribution of dust to plant biomass growth over the past 2000 years - Lin Chen; Youliang Huang; Menghan Qiu; Zhilun Li; Rui Yang; Mengjing Li; Huiling Sun; Lixiong Xiang; Shanjia Zhang; Xiaozhong Huang; Aifeng Zhou (Global and Planetary Change, 2025)

An investigation of the mechanism of emulsion stabilization in octenyl succinic anhydride-modified tamarind seed polysaccharide - Yuxing Kou; Rui Guo; Xianbao Sun; Xuan Ma; Yinan Chen; Lihua Song; Zibo Song; Chunmei Yuan; Siyan Huang; Jian Tang; Yan Wu (Food Hydrocolloids, 2025)

Rheology, stability, and physicochemical properties of NaOH-tannic acid solvent for β-chitin dissolution - Shang-Ta Wang; Po-Jou Huang; Szu-Kai Chen; Chia-Rui Shen; Yi-Pin Chen; Min-Lang Tsai (Food Hydrocolloids, 2025)

Effect of the Hofmeister series anion salts on the ice recrystallization inhibition activity of tamarind seed polysaccharide - Xianbao Sun; Shihao Dai; Rui Guo; Taijie Zhan; Fan Xie; Yuxing Kou; Xuan Ma; Yinan Chen; Lihua Song; Hui Zhang; Lu Ren; Chunmei Yuan; et al. (Food Hydrocolloids, 2025)

Reversible multilevel stimuli-responsiveness and multicolor room temperature phosphorescence to fluorescence transition based on a metal–organic framework system - Hui-Li Sun; Zhong-Hao Wang; Rui-Qi Huang; Zhuo-Di Chen; Mei Pan (Chemical Engineering Journal, 2025)

Enhanced wastewater treatment using biochar-supported layered-double-hydroxide composites - Ao Huang; Nan Zhang; Qian-Bin Wang; Bo-Han Zhao; Rui-Bao Zhang; Ming Cheng; Chen Shi; Xiao-Di Hao (Chemical Engineering Journal, 2025)

Flowering delay in apple could alleviate frost-induced yield loss under climate change in China - Renwei Chen; Jing Wang; Bin Wang; Yang Li; Rui Bai; Mingxia Huang; Zhenjiang Qu; Lu Liu (Agricultural and Forest Meteorology, 2025)

A novel hybrid model for air quality prediction via dimension reduction and error correction techniques - Rui Huang; Rui Hu; Huayou Chen (Environmental Monitoring and Assessment, 2024)

Tracing contaminants of emerging concern and their transformations in the whole treatment process of a municipal wastewater treatment plant using nontarget screening and molecular networking strategies - Zhenguo Chen; Di Xia; Huangrui Liu; Rui Wang; Mingzhi Huang; Ting Tang; Guining Lu (Water Research, 2024)

Distribution, transport and ecological risk prediction of organophosphate esters in China seas based on machine learning - Rui Chen; Wenyang Huang; Linlin Sun; Jingyan Yang; Tiantian Ma; Rongguang Shi (Science of The Total Environment, 2024)

Molecular characteristics of dissolved organic matter regulate the binding and migration of tungsten in porous media - Weijun Li; Jian Xie; Rui Huang; Wei Chen; Huihui Du (Science of The Total Environment, 2024)

Reduced phytoplankton biomass in a subtropical plume-upwelling system induced by typhoons Bailu and Podul - Zhuyin Tong; Lingqi Ma; Shujie Cai; Zhaoyun Chen; Lei Wang; Mingwang Xiang; Rui Huang; Meilin Wu; Wupeng Xiao; Bangqin Huang (Progress in Oceanography, 2024)

Natural and anthropogenic forcing of ecological and environmental changes at Lake Qilu, SW China, since the last deglaciation - Kaiyu Cao; Lin Chen; Yongxiu Lu; Yao Zhang; Mengjing Li; Duo Wu; Yilong Wang; Liang Chen; Xiaonan Zhang; Rui Yang; Youliang Huang; Aifeng Zhou (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Manganese exposure leads to depressive-like behavior through disruption of the Gln–Glu–GABA metabolic cycle - Yujie Bi; Nannan Huang; Duo Xu; Shenshen Wu; Qingtao Meng; Hanqing Chen; Xiaobo Li; Rui Chen (Journal of Hazardous Materials, 2024)

Comparative organic pollutants removal efficiency and life cycle assessment of pyrolysis and solvent elution for industrial waste salt recycling - Xinyu Huang; Hao Wang; Min Song; Rui Chen; Saijun Lv; Haoqing Zhang; Chuqi Wang; Jerome Ramirez; Xiuxiu Ruan (Journal of Environmental Management, 2024)

Study on volatile metabolites and microbial community in the fermentation process of black tea (Jiuqu hongmei tea) - Shanshan Li; Jiaxin Huang; Xueping Chen; Rui Shen; Han Jiang; Guangfa Xie; Qi Peng (International Journal of Gastronomy and Food Science, 2024)

Phosvitin phosphopeptides and peptides-calcium chelate promote calcium deposition in a three-cell co-culture system by modulating the OPG/RANKL/RANK signaling pathway - Jiaojiao Chen; Songming Li; Mahmoud Abou-Elsoud; Wei Liu; Rui Cui; Zuyue Li; Dewei Shu; Zhaoxia Cai; Xi Huang (Food Bioscience, 2024)

Impact of mutations in carbohydrate binding sites of tandem-repeat type galectin from Takifugu obscurus on its antimicrobial activity - Ying Huang; Li-Fan Cui; Rui Shen; Ding-Yi Chen; Min Jin; Xue Jiao; Yu-Guang Chen; Ming-Xuan Pan; Ya-Dong Hu; Zhe Zhao (Fish & Shellfish Immunology, 2024)

Groundwater resistant gene accumulation in mining-agriculture complex zones: Insights from metagenomic analysis of subterranean mineral and terrestrial agricultural interactions - Rui Wang; Ping Lu; Fangfang Chen; Yanchang Huang; Haoran Ding; Tianhang Cheng (Environmental Research, 2024)

The remediation performance and mechanism for tetracycline from groundwater using controlled release materials containing mesoporous MnOx with different morphology - Ting Wang; Jing-le Chen; Rui Huang; Li-guang Wu; Kou-ping Chen; Ji-chun Wu; Hua-li Chen (Environmental Pollution, 2024)

Deciphering the biodegradation mechanism of 3,6-dichlorocarbazole using a novel isolate for its implication in bioaugmentation - Mi Feng; Rui Zhou; Zhaolong Zhu; Yantian Xie; Minghan Zhu; Zhanyu Guo; Xinghui Feng; Dongxia Fu; Jianhua Chen; Yanhong Du; Yao Huang (Chemical Engineering Journal, 2024)

Sub-millimeter scale 3D integration strategy enables ultrahigh-density and ultralow-crosstalk flexible tactile sensor array for robotic e-skin application - Shaoxiong Hu; Rui Wang; Wei Zhu; Yue Huang; Ying Li; Yuchen Yang; Qingqing Zhang; Yuedong Yan; Chen Lin; Yuan Deng (Chemical Engineering Journal, 2024)

Sample-to-answer point-of-care testing platform for quantitative detection of small molecules in blood using a smartphone-and microfluidic-based nanoplasmonic biosensor - Hongli Fan; Rui Li; Youqian Chen; Qiang Da; Chenchen Xiong; Yiyi Zhang; Zhiguo Qin; Gang L. Liu; Liping Huang (Chemical Engineering Journal, 2024)

Lipid nanoparticle-mediated base-editing of the Hao1 gene achieves sustainable primary hyperoxaluria type 1 therapy in rats - Dexin Zhang; Rui Zheng; Zhoutong Chen; Liren Wang; Xi Chen; Lei Yang; Yanan Huo; Shuming Yin; Dan Zhang; Jiaxin Huang; Xingang Cui; Dali Li; et al. (Science China Life Sciences, 2024)

Analysis of deliquescent chloride salt by laser-induced breakdown spectroscopy with controlled uniform precipitation - Lizhu Kang; Ji Chen; Zhijie Huang; Zhanjian Lin; Rui Zhang; Bing Lu; Xiangyou Li (Analytica Chimica Acta, 2024)

Optimal operation of CCHP system with duality operation strategy considering hydrogen trading and carbon capture - Zhi-Feng Liu; Ya-He Huang; Qing Kang; Ze-Qi Li; Jing Lu; Rui-Zheng Gu; Xing-Fu Luo; Xiao-Rui Chen; You-Yuan Liu; Yu Tang; Liang Guo (Sustainable Cities and Society, 2024)

The creation of multi-level urban ecological cooling network to alleviate the urban heat island effect - Yingying Li; Shumei Wang; Shujun Zhang; Min Wei; Yongsheng Chen; Xiaoyi Huang; Rui Zhou (Sustainable Cities and Society, 2024)

Dissecting the characteristics and driver factors of potential vegetation water use efficiency in China - Rui Kong; Bin Zhu; Zengxin Zhang; Ying Zhang; Richao Huang; Xi Chen; Chong-Yu Xu (Science of The Total Environment, 2024)

Assessing soil remediation effect of Cr and Pb based on bioavailability using DGT, BCR and standardized determination method - Rui Chen; Jingyan Yang; Xuying Cai; Zean Liu; Wenyang Huang; Rongguang Shi; Tiantian Ma (Science of The Total Environment, 2024)

Comparison of prenatal and postnatal exposure to neonicotinoids and their temporal trends in breast milk - Kaiqin Huang; Meiqing Lin; Jing Yi; Guocheng Liu; Rui Hua; Yangyang Liu; Yanji Qu; Cairong Chen; Shengtao Ma (Science of The Total Environment, 2024)

KMT2D deficiency leads to cellular developmental disorders and enhancer dysregulation in neural-crest-containing brain organoids - Ziyun Shan; Yingying Zhao; Xiuyu Chen; Guodong Zhan; Junju Huang; Xuejie Yang; Chongshen Xu; Ning Guo; Zhi Xiong; Fang Wu; Yujian Liu; He Liu; et al. (Science Bulletin, 2024)

Preparation and properties of cationic starch-carrageenan‑sodium alginate hydrogels with pH and temperature sensitivity - Zheng Cai; Wei Zhou; Wenjing Chen; Rui Huang; Rui Zhang; Li Sheng; Miaomiao Shi; Yong Hu; Chao Huang; Yun Chen (Food Chemistry, 2024)

Dynamics of impure CO2 and composite oil in mineral nanopores: Implications for shale oil recovery and gas storage performance - Lu Wang; Run Zou; Yifan Yuan; Yifan Zhang; Rui Zou; Liang Huang; Yisheng Liu; Zhan Meng; Hao Chen (Chemical Engineering Journal, 2024)

Formation of flake-like DAAF crystals with tunable size realized on a microfluidic platform for binder-free initiator explosives - Bo Yang; Shengshu Xi; Simin He; Jin Chen; Wei Cao; Rui Li; Rupeng Bu; Xiaona Huang; Jincan Zhu; Qi Wu; Weimiao Wang; Xiaodong Li; et al. (Chemical Engineering Journal, 2024)

Sustainable rewritable paper based on photoresponsive tungsten oxide quantum dots for anti-counterfeiting and waterproofing - Tiandi Chen; Xiaoxue Mai; Yiyun Li; Tingting Wang; Rui Gong; Feixiong Chen; Hongjie Huang; Zhiyong Yan; Feng Wang (Chemical Engineering Journal, 2024)

A miniaturized microfluidic nanoplasmonic sensor with cavity reflection enhancement for ultrasensitive molecular interaction analysis - Hongli Fan; Mingqian Chen; Rui Li; Youqian Chen; Shaoqi Zeng; Wenjun Hu; Gang L. Liu; Chunmeng Sun; Liping Huang (Chemical Engineering Journal, 2024)

The CYP3A inducer dexamethasone affects the pharmacokinetics of sunitinib by accelerating its metabolism in rats - Guang-rong Lu; Rui-zhen Wang; Xin-yu Zhao; Jun-er Xu; Cheng-ke Huang; Wei Sun; Rui-jie Chen; Zhe Wang (Chemico-Biological Interactions, 2024)

Shifts in reproductive strategies in the evolutionary trajectory of plant lineages - Xin-Jian Zhang; Xian-Han Huang; Jacob B. Landis; Quan-Sheng Fu; Jun-Tong Chen; Peng-Rui Luo; Li-Juan Li; Heng-Yi Lu; Hang Sun; Tao Deng (Science China Life Sciences, 2024)

Relative importance of altitude shifts with plant and microbial diversity to soil multifunctionality in grasslands of north-western China - Ning Wang; Junhui Cheng; Yunhua Liu; Qicheng Xu; Chen Zhu; Ning Ling; Junjie Guo; Rui Li; Wei Huang; Shiwei Guo; Baorong Wang; Shaoshan An; et al. (Plant and Soil, 2024)

Shifts in organic carbon protection mechanism in agricultural soils across climatic gradients - Chong Ma; Yinhang Xia; Yichao Rui; Wei Gao; Xun Duan; Hang Qiao; Xunyang He; Yajun Hu; Daoyou Huang; Jinshui Wu; Yirong Su; Georg Guggenberger; et al. (Agriculture, Ecosystems & Environment, 2024)

Association Between Zinc Ion Concentrations in Seminal Plasma and Sperm Quality: A Chinese Cross-Sectional Study - Gangxin Chen; YeBin Feng; Rui Yang; Haiyan Li; Zhiqin Huang; Zhihao Li; Beihong Zheng; Yan Sun (Biological Trace Element Research, 2024)

A bifunctional amylopullulanase of Streptococcus suis ApuA contributes to immune evasion by interaction with host complement C3b - Jiajia Xu; Jiaqi Zhu; Weiyao Han; Siqi Pang; Simin Deng; Long Chen; Xiabing Chen; Qi Huang; Rui Zhou; Lu Li (Veterinary Microbiology, 2024)

Macroalgal fossil Longfengshania from the Tonian Shiwangzhuang and Jiuliqiao formations in western Shandong and northern Anhui, North China - Guang-Jin Li; Lei Chen; Ke Pang; Qing Tang; Cheng-Xi Wu; Rui Huang; Ming-Yang Qiu; Xun-Lai Yuan; Chuan-Ming Zhou (Palaeoworld, 2024)

Fabrication and characterization of oxidized starch-xanthan gum composite nanoparticles with efficient emulsifying properties - Zheng Cai; Wei Zhou; Rui Zhang; Yuqi Tang; Kun Hu; Fangfang Wu; Chao Huang; Yong Hu; Tao Yang; Yun Chen (Food Chemistry, 2024)

The effects of kelp powder and fucoidan on the intestinal digestive capacity, immune response, and bacterial community structure composition of large yellow croakers (Larimichthys crocea) - Qiqin Liu; Guoyi Li; Sifeng Zhu; Juanjuan Chen; Min Jin; Chengwei Huang; Liyue Chai; Liegang Si; Rui Yang (Fish & Shellfish Immunology, 2024)

Chronic PM2.5 exposure disrupts intestinal barrier integrity via microbial dysbiosis-triggered TLR2/5-MyD88-NLRP3 inflammasome activation - Zihan Ran; Jingcheng Yang; Liang Liu; Shaobo Wu; YanPeng An; Wanwan Hou; Tianyuan Cheng; Youyi Zhang; Yiqing Zhang; Yechao Huang; Qianyue Zhang; Jiaping Wan; et al. (Environmental Research, 2024)

Bismuth nanosheets guided zinc deposition enabled long-life aqueous zinc-based flow batteries - Yizhe Nie; Huang Chen; Jiajun Wu; Rui Nie; Lihong Yu; Le Liu; Jingyu Xi (Chemical Engineering Journal, 2024)

Electric field-driven assembly of (110) oriented metal–organic framework ZIF-8 monolayer with high hydrogen selectivity - Chunxin Jin; Shuai Liu; Rui Zheng; Yanhong Li; Xiaofang Chen; Jürgen Caro; Jianwen Jiang; Aisheng Huang (Chemical Engineering Journal, 2024)

An efficient Au/ZnO catalyst for the photocatalytic conversion of methane to formaldehyde - Yan-Qun Chen; Lei-Xin Mao; Rui-Xin Zhang; Xin-Yu Zhang; Zhi-Hua Gao; Lei Liu; Wei Huang; Zhi-Jun Zuo (Chemical Engineering Journal, 2024)

Suppression the glucose-induced ferroptosis in endothelial cells by 4OI-loading exosomes hydrogel for the treatment of diabetic foot ulcer - Kuo Shen; Rui Zheng; Bangrui Yu; Hao Zhang; Peng Wang; Peng Zhao; Jijun Chen; Yixuan Yuan; Yuhang Wang; Kejia Wang; Yanhui Jia; Ruizhi Wang; et al. (Chemical Engineering Journal, 2024)

Facile generation of unsaturated-coordinated and atomically-dispersed hafnium active sites for the highly efficient catalytic transfer hydrogenation of levulinic acid - Rulu Huang; Yue Wang; Feiyi Chen; Huai Liu; Rui Zhang; Wenlong Jia; Lincai Peng; Yong Sun; Junhua Zhang (Chemical Engineering Journal, 2024)

Investigating thermal exposure during daily walking through a human-scale approach: An analysis of a hot summer in Wuhan - Jiwei Xu; Xinkun Xu; Zimeng Wang; Huiting Chen; Qiran Ren; He Huang; Yao Cui; Rui An; Yaolin Liu (Building and Environment, 2024)

The role of male hormones in bacterial infections: enhancing Staphylococcus aureus virulence through testosterone-induced Agr activation - Zhaoxia Luo; Huimin Xi; Wei Huang; Mei-fang Liu; Lei Yuan; Qiang Chen; Yanghua Xiao; Qing Zhu; Rui Zhao; Yi-yun Sheng (Archives of Microbiology, 2024)

Exposure to Multiple Metal(loid)s and Hypertension in Chinese Older Adults - Rui Zhang; JiaMou Zhou; PengCheng Huo; HeQiao Zhang; HuiYan Shen; Qian Huang; GuiMei Chen; LinSheng Yang; DongMei Zhang (Biological Trace Element Research, 2024)

Short-term exposure to ambient fine particulate matter constituents and myocardial infarction mortality - Yingxin Li; Bing Lu; Jing Wei; Qingqing Wang; Wancheng Ma; Rui Wang; Ruijun Xu; Zihua Zhong; Lu Luo; Xi Chen; Ziquan Lv; Suli Huang; et al. (Chemosphere, 2024)

Improved monitoring of southern corn rust using UAV-based multi-view imagery and an attention-based deep learning method - Zhengang Lv; Binyuan Xu; Liheng Zhong; Gengshen Chen; Zehua Huang; Rui Sun; Wei Huang; Feng Zhao; Ran Meng (Computers and Electronics in Agriculture, 2024)

Backwater makes the tributaries of large river becoming phosphorus “sink” - Bingfen Cheng; Yuan Zhang; Rui Xia; Guoxian Huang; Tianlin Qin; Denghua Yan; Yan Chen (Water Research, 2024)

A novel OsGST gene encoding 9glutathione reductase negatively regulates cadmium accumulation in rice - Rui Guo; Su Li; Yong Qiang Gao; Jia Tong He; Hao Yu Wang; Jin Chen; Jiu Huang; Ren Fang Shen; Xiao Fang Zhu (Journal of Hazardous Materials, 2024)

Hotspots lurking underwater: Insights into the contamination characteristics, environmental fates and impacts on biogeochemical cycling of microplastics in freshwater sediments - Haojie Chen; Danlian Huang; Wei Zhou; Rui Deng; Lingshi Yin; Ruihao Xiao; Sai Li; Fei Li; Yang Lei (Journal of Hazardous Materials, 2024)

Higher risk of spring frost under future climate change across China's apple planting regions - Renwei Chen; Jing Wang; Yang Li; Rui Bai; Mingxia Huang; Zhenzhen Zhang; Lingxuan Zhao; Zhenjiang Qu; Lu Liu (European Journal of Agronomy, 2024)

Advanced Fe-COF-based photothermal cascade nano-generator for sterilization and promoting wound healing - Xingyu Wu; Tiantian Feng; Xiaohong Zhu; Dong Dong; Qinxue Gao; Shufan Huang; Rui Huang; Dong Wang; Huayu Xiong; Zigong Wei; Yong Chen; Jichao Liang (Chemical Engineering Journal, 2024)

Photo-crosslinking modified gelatin-silk fibroin hydrogel for accelerating wound repair of open abdomen - Ye Liu; Sicheng Li; Jinjian Huang; Xuanheng Li; Ze Li; Canwen Chen; Guiwen Qu; Kang Chen; Yitian Teng; Rui Ma; Xiuwen Wu; Jianan Ren (Chemical Engineering Journal, 2024)

Liquidizing crystal MIL-100(Fe) to coating silica powder for purifying wastewater - Shiyong Wei; Aijia Cao; Siyuan Huang; Yao Shen; Ting Lei; Songmei Luo; Mingjun Cai; Wenjun Xiang; Anying Chen; Rui Wang (Chemical Engineering Journal, 2024)

Recent progress in carbonaceous materials for the hydrogen cycle: Electrolytic water splitting, hydrogen storage and fuel cells - Guanghui Xia; Habibullah; Qingfeng Xie; Qin Huang; Meitong Ye; Bingshou Gong; Rui Du; Yao Wang; Yigang Yan; Yungui Chen; Chaoling Wu (Chemical Engineering Journal, 2024)

MARCH1 and MARCH2 inhibit pseudorabies virus replication by trapping the viral cell-to-cell fusion complex in trans-Golgi network - Rui Huang; Cui-Hong Rao; Yuan-Zhe Bai; Changqing Yu; Meng Chen; Jin-Mei Peng; Shi-Jia Xu; Yue Sun; Meng Fandan; Chuang Lyu; Mirwaise Khan; Tong-Qing An; et al. (Veterinary Microbiology, 2024)

Phase I clinical trial of intracerebral injection of lentiviral-ABCD1 for the treatment of cerebral adrenoleukodystrophy - Qiu-Hong Wang; Jing Wang; Zhi-Pei Ling; Zhi-Qiang Cui; Jie Gong; Rui Zhang; Shi-Jun Li; Yang-Yang Wang; Rui Yang; De-Hui Huang; Wen He; Jing Gao; et al. (Science Bulletin, 2024)

Synthesis of a graphene oxide-based zerovalent iron nanocomposite for efficient remediation of Re(VII) from simulated wastewater in high pH - Yixin Pan; Yanbin Cai; Lujia Chen; Leilei Sun; Liping Deng; Rui Huang (Journal of Water Process Engineering, 2024)

Computational tools for plant genomics and breeding - Hai Wang; Mengjiao Chen; Xin Wei; Rui Xia; Dong Pei; Xuehui Huang; Bin Han (Science China Life Sciences, 2024)

Stefin B alleviates the gouty arthritis in mice by inducing the M2 polarization of macrophages - Shishui Lin; Xu Hu; Yang Li; Jiyue Huang; Rui Zhang; Xinxin Bai; Shaohuang Weng; Min Chen (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)
The present study aims to explore the therapeutic effect of Stefin B on gouty arthritis (GA) and the polarization of macrophages in mice. Stefin B-overexpressed or knockdown M0 macrophages were constructed. The GA model was established in mice by injecting 25 mg/mL MSU, followed by a single injecting of Stefin B-overexpressing adenovirus vector (GA model + Stefin B OE) or an empty vector (GA model + Stefin B OE NC). Stefin B was found lowly expressed in M1 macrophages. CD206 was markedly upregulated and IL-10 release was signally increased in Stefin B-overexpressed macrophages. In gouty arthritis mice, marked redness and swelling were observed in the ankle joint. Dramatical infiltration of inflammatory cells was observed in the GA model and GA model + Stefin B OE NC groups, which was suppressed in the Stefin B OE group. Increased proportion of F4/80 + CD86 + cells observed in GA mice was markedly repressed by Stefin B overexpression, accompanied by the declined level of Caspase-1 and IL-17. Collectively, Stefin B alleviated the GA in mice by inducing the M2 polarization of macrophages.

Diagnostic performance of mpox virus (MPXV) real-time PCR assays: multicenter assessment and extended sensitivity analysis - Ziqiang Li; Yuqing Chen; Yanxi Han; Zhenli Diao; Tao Huang; Lei Feng; Yu Ma; Cong Liu; Meng Tian; Jing Li; Wanyu Feng; Zihong Zhao; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

SAD2 functions in plant pathogen Pseudomonas syringae pv tomato DC3000 defense by regulating the nuclear accumulation of MYB30 in Arabidopsis thaliana - Tiantian Shi; Yuan Zheng; Rui Wang; Sha Li; Andi Xu; Luoying Chen; Yuanhang Liu; Rong Luo; Chenchen Huang; Yinglu Sun; Jinfeng Zhao; Xiaoying Guo; et al. (Plant Science, 2024)

Ent-eudesmane sesquiterpenoids with anti-neuroinflammatory activity from the marine-derived fungus Eutypella sp. F0219 - Zhong-Ping Jiang; Rui Su; Meng-Ting Chen; Jun-Yi Li; Han-Yu Chen; Lu Yang; Fei-Fei Liu; Jin Liu; Cong-Jun Xu; Wan-Shan Li; Yong Rao; Ling Huang (Phytochemistry, 2024)

Corrigendum to “Brassinosteroid decreases cadmium accumulation via regulating gibberellic acid accumulation and Cd fixation capacity of root cell wall in rice (Oryza sativa)” J Hazard Mater 469(2024) 133862 - Jie Ya Sun; Rui Guo; Qi Jiang; Chang Zhao Chen; Yong Qiang Gao; Meng Meng Jiang; Ren Fang Shen; Xiao Fang Zhu; Jiu Huang (Journal of Hazardous Materials, 2024)

Effect of annealing treatment on physicochemical properties, rheology and in vitro digestion of potato starch-galactomannan complexes - Rui Zhang; Rui Huang; Zheng Cai; Yuqi Tang; Yong Hu; Chao Huang; Nanjing Zhong; Yun Chen (Food Hydrocolloids, 2024)

Amorphous/Graphitic carbon phase engineering of Corrosion-Resistant Fe@C Core-Shell nanowires for optimized dipole polarization and enhanced microwave absorption - Ping-an Yang; Wenjiao Deng; Haibo Ruan; Zhengwei Qu; Rui Li; Lirui Wang; Jiufei Luo; Zhihao Zhou; Mengjie Shou; Xin Huang; Qiao Chen; Xinglong Gong (Chemical Engineering Journal, 2024)

Dissecting the negative influence mechanisms of microplastics on plant and microbial mediated nitrogen removal in constructed wetlands - Yixuan Ma; Juan Huang; Rui Li; Xuan Chen; Meifang Cao (Chemical Engineering Journal, 2024)

Sustainable reprocessing of lithium iron phosphate batteries: A recovery approach using liquid-phase method at reduced temperature - Tingyan Ren; Bolin Zou; Bin Cai; Tong Liang; Junhao Chen; Rui Huang; Dahai Yang; Hongfa Xiang; Edison Huixiang Ang; Xiaohui Song (Waste Management, 2024)

Corrigendum to “Silicon in soil and its interaction with nitrogen, phosphorus, and potassium nutrients on rice yield: A case study of paddy fields in the Taihu Lake region, China, without a history of silicon fertilization” [Soil Tillage Res. 238 (2024) 106027] - Sihua Huang; Lijie Pu; Gaili He; Xiaoqing Wang; Dejing Chen; Xuefeng Xie; Lu Qie; Yang Dan; Rui Zhang; Zhongshun Gong; Yumeng Lu (Soil and Tillage Research, 2024)

Enhancing long-term river water quality prediction: Construction and validation of an improved hybrid model - Yadan Yu; Yangwu Chen; Shunbo Huang; Rui Wang; Houzhen Zhou; Chuankun Liu; Wei Wang; Zhouliang Tan (Process Safety and Environmental Protection, 2024)

Investigation of collagen reconstruction mechanism in skin wound through dual-beam laser welding: Insights from multi-spectroscopy, molecular dynamics simulation, and finite element multiphysics simulation - Yuxin Chen; Laura Forster; Kehong Wang; Himadri S. Gupta; Xiaopeng Li; Jun Huang; Yunfeng Rui (Journal of Photochemistry and Photobiology B: Biology, 2024)

High variation of worker cell and morphology between two adjacent populations of honey bee, Apis cerana (Hymenoptera, Apidae) - Rui Zhu; Weilai Zhong; Yuhui Chen; Guiling Ding; Zhanbao Guo; Jiaxing Huang (Journal of Asia-Pacific Entomology, 2024)

Near-infrared laser induced direct ignition of 4,4′,5,5′-tetranitro-1H,1′H-[2,2′-biimidazole]-1,1′-diamine by constructing diverse crystal structures - Ping Ye; Weimiao Wang; Xiaodong Li; Zhiqiang Qiao; Yirui Lu; Bing Huang; Liangfei Bai; Liang Chen; Xiaoqing Tu; Rui Li; Guangcheng Yang; Guoqing Lv (Chemical Engineering Journal, 2024)

Regulatory effect of Yinchenhao decoction on bile acid metabolism to improve the inflammatory microenvironment of hepatocellular carcinoma in mice - Jian Shi; Lin Zhu; Bang-Yi Tang; Wan-Qing Yang; Sheng-Yan Xi; Chen-Long Zhang; Peng-Fei Li; Yu-Jie Wang; Kai-Hang Guo; Jing-Ru Huang; Chen-Rui Huang; Zhou-Xin Yu; et al. (Journal of Natural Medicines, 2024)

Silicon in soil and its interaction with nitrogen, phosphorus, and potassium nutrients on rice yield: A case study of paddy fields in the Taihu Lake region, China, without a history of silicon fertilization - Sihua Huang; Lijie Pu; Gaili He; Xiaoqing Wang; Dejing Chen; Xuefeng Xie; Lu Qie; Yang Dan; Rui Zhang; Zhongshun Gong; Yumeng Lu (Soil and Tillage Research, 2024)

Regional scale terrace mapping in fragmented mountainous areas using multi-source remote sensing data and sample purification strategy - Zicheng Liu; GuoKun Chen; Bohui Tang; Qingke Wen; Rui Tan; Yan Huang (Science of The Total Environment, 2024)

Enhancing the effluent prediction accuracy with insufficient data based on transfer learning and LSTM algorithm in WWTPs - Yadan Yu; Yangwu Chen; Shunbo Huang; Rui Wang; Yadong Wu; Houzhen Zhou; Xin Li; Zhouliang Tan (Journal of Water Process Engineering, 2024)

Experimental and numerical investigations on soil–water dynamics in Moistube irrigation under dynamically regulated working pressure heads: scenario simulations under maize cultivation - Jinyang Ye; Ce Wang; Xiaoan Chen; Wuerkaixi Kurexi; Mingyi Huang; Zhengyu Duan; Rui Xu; Yuanjie Li; Zeyang Zhang (Journal of Hydrology, 2024)

A novel aldo-keto reductase gene, OsAKR1, from rice confers higher tolerance to cadmium stress in rice by an in vivo reactive aldehyde detoxification - Rui Guo; Qiang Zhang; Chang Zhao Chen; Jie Ya Sun; Chun Yan Tu; Meng Xing He; Ren Fang Shen; Jiu Huang; Xiao Fang Zhu (Journal of Hazardous Materials, 2024)

A near-infrared fluorescent ratiometric probe with large Stokes shift for multi-mode sensing of Pb2+ and bioimaging - Cuibing Bai; Junxiong Yao; Qian Meng; Yajie Dong; Mengyu Chen; Xinyi Liu; Xinyu Wang; Rui Qiao; Huanan Huang; Biao Wei; Changqing Qu; Hui Miao (Journal of Hazardous Materials, 2024)

Brassinosteroid decreases cadmium accumulation via regulating gibberellic acid accumulation and Cd fixation capacity of root cell wall in rice (Oryza sativa) - Jie Ya Sun; Rui Guo; Qi Jiang; Chang Zhao Chen; Yong Qiang Gao; Meng Meng Jiang; Ren Fang Shen; Xiao Fang Zhu; Jiu Huang (Journal of Hazardous Materials, 2024)

Tradeoffs between pH, dissolved organic carbon, and mineral ions regulate cadmium uptake by Solanum hyperaccumulators in calcareous soil - Rui Wang; Zhihao Xu; Shuai Chen; Jieqiong Su; Yu Huang; Yahu Hu (Environmental Research, 2024)

Physiological responses and molecular mechanisms of biofilm formation induced by extracellular metabolites of euglena in Pseudomonas aeruginosa LNR1 for diesel biodegradation based on transcriptomic and proteomic - Guotao Chen; Huiqun Zhang; Meng Yuan; Rui Huang; Yibo Xiao; Yujiao Qu; Yuan Ren (Environmental Research, 2024)

Comparative study of reactive oxygen species and tetracycline degradation pathways in catalytic peroxodisulfate activation by asymmetric mesoporous TiO2 and the corresponding controlled-release materials - Ting Wang; Rui Huang; Hua-Li Chen; Kun-Miao Xu; Li-Guang Wu; Kou-Ping Chen; Ji-Chun Wu (Environmental Pollution, 2024)

Revealing the electrochemical-mechanical correspondence between electrode films and 20 Ah prismatic Li-ion batteries via optical fiber monitoring - Xiaoyu Ge; Yi Zhang; Rui Du; Nian Chen; Yifei Yu; Zhen Li; Yunhui Huang (Chemical Engineering Journal, 2024)

Carboxymethyl chitosan-based hydrogel-Janus nanofiber scaffolds with unidirectional storage-drainage of biofluid for accelerating full-thickness wound healing - Xinhao Chen; Hui Huang; Xinru Song; Ting Dong; Jiafei Yu; Jieyan Xu; Rui Cheng; Tingting Cui; Jun Li (Carbohydrate Polymers, 2024)

Beneficial action of cinnamic acid against ovarian cancer via network pharmacology analysis and the pharmacological activity assessment - Rong Fan; Zining Liang; Qing Wang; Sizhe Chen; Shiting Huang; Jiansu Liu; Rui Huang; Jie Chen; Feilan Zhao; Wei Huang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Proteomics Sequencing Reveals the Role of TGF-β Signaling Pathway in the Peripheral Blood of Offspring Rats Exposed to Fluoride - Fang-fang Yu; Shui-yuan Yu; Lei-zhen Duan; Shuo Yang; Xiang-bo Hou; Yu-hui Du; Ming-hui Gao; Juan Zuo; Lei Sun; Xiao-li Fu; Zhi-yuan Li; Hui Huang; et al. (Biological Trace Element Research, 2024)

A novel framework for high resolution air quality index prediction with interpretable artificial intelligence and uncertainties estimation - Junhao Wu; Xi Chen; Rui Li; Anqi Wang; Shutong Huang; Qingli Li; Honggang Qi; Min Liu; Heqin Cheng; Zhaocai Wang (Journal of Environmental Management, 2024)

Self-powered Fenton-like process for propranolol degradation and bacterial inactivation with Mg-CuO/CeO2/BC composites - Yanchao Jin; Xiongjian Chen; Peiwen Huang; Chun-Yan Lin; Rui Ding; Riyao Chen (Journal of Environmental Chemical Engineering, 2024)

Synergistic removal of sulphur-containing malodourous gases via peroxydisulfate activation in three-dimensional electrode system - Rui Luo; Shugen Liu; Chen Li; Xiaofeng Huang; Ping Ning; Senlin Tian (Journal of Environmental Chemical Engineering, 2024)

Rapid quality evaluation and geographical origin recognition of ginger powder by portable NIRS in tandem with chemometrics - Rui Chen; Shaoqun Li; Huijuan Cao; Tongguang Xu; Yanchang Bai; Zhanming Li; Xiaojing Leng; Yue Huang (Food Chemistry, 2024)

Pilot-scale investigation of performance and microbial community in a novel system combining fixed and suspended activated sludge - Dongni Rui; Kunlong Liu; Yanyan Ma; Kailong Huang; Mengxue Chen; Fei Wu; Xuxiang Zhang; Lin Ye (Environmental Research, 2024)

Mechanisms of benzene and benzo[a]pyrene biodegradation in the individually and mixed contaminated soils - Mukhtiar Ali; Qing Wang; Zhuanxia Zhang; Xing Chen; Min Ma; Zhiwen Tang; Rui Li; Biao Tang; Zhongyuan Li; Xiangfeng Huang; Xin Song (Environmental Pollution, 2024)

Modeling investigation of wave-induced longshore current distribution patterns on barred beaches - Chao Ji; Qinghe Zhang; Tongqing Chen; Dianguang Ma; Rui Huang (Estuarine, Coastal and Shelf Science, 2024)

Effect of Regional Brain Activity Following Repeat Transcranial Magnetic Stimulation in SCA3: A Secondary Analysis of a Randomized Clinical Trial - Xia Liu; Lin Zhang; Hao-Lin Xu; Xia-Hua Liu; Arif Sikandar; Meng-Cheng Li; Xiao-Yue Xia; Zi-Qiang Huang; Na-Ping Chen; Yu-Qing Tu; Jian-Ping Hu; Shi-Rui Gan; et al. (The Cerebellum, 2024)

Characterization of CYP82 genes involved in the biosynthesis of structurally diverse benzylisoquinoline alkaloids in Corydalis yanhusuo - Xiuyu Liu; Ying Ma; Junling Bu; Conglong Lian; Rui Ma; Qishuang Li; Xiang Jiao; Zhimin Hu; Yun Chen; Suiqing Chen; Juan Guo; Luqi Huang (Plant Molecular Biology, 2024)

Endophytic Enterobacter sp. YG-14 mediated arsenic mobilization through siderophore and its role in enhancing phytostabilization - Jiawei Chen; Xuan Zhang; Min Kuang; Kunpeng Cui; Ting Xu; Xuanming Liu; Rui Zhuo; Ziwei Qin; Zhigang Bu; Zhongliang Huang; Hui Li; Jing Huang; et al. (Journal of Hazardous Materials, 2024)

Preparation and properties of pH-sensitive cationic starch nanoparticles - Wei Zhou; Rui Zhang; Zhen Cai; Fangfang Wu; Yong Hu; Chao Huang; Kun Hu; Yun Chen (Food Chemistry, 2024)

From Western centralism to decentralization: Trends, breakthroughs and limitations in the world city network based on the winter olympic games - Yubin Ou; Gengzhi Huang; Rui Chen; Hua Chen; Anan Xie; Desheng Xue (Applied Geography, 2024)

Deep learning in water protection of resources, environment, and ecology: achievement and challenges - Xiaohua Fu; Jie Jiang; Xie Wu; Lei Huang; Rui Han; Kun Li; Chang Liu; Kallol Roy; Jianyu Chen; Nesma Talaat Abbas Mahmoud; Zhenxing Wang (Environmental Science and Pollution Research, 2024)

Effects of short and long-term thermal exposure on microbial compositions in soils contaminated with mixed benzene and benzo[a]pyrene: A short communication - Mukhtiar Ali; Xin Song; Qing Wang; Zhuanxia Zhang; Meng Zhang; Min Ma; Jilu Che; Rui Li; Xing Chen; Zhiwen Tang; Biao Tang; Xiangfeng Huang (Science of The Total Environment, 2024)

PD-L1 expression guidance on sintilimab versus pembrolizumab with or without platinum-doublet chemotherapy in untreated patients with advanced non-small cell lung cancer (CTONG1901): A phase 2, randomized, controlled trial - Si-Yang Maggie Liu; Jie Huang; Jia-Yi Deng; Chong-Rui Xu; Hong-Hong Yan; Ming-Yi Yang; Yang-Si Li; E-E Ke; Ming-Ying Zheng; Zhen Wang; Jia-Xin Lin; Bin Gan; et al. (Science Bulletin, 2024)

Chuaria and Tawuia fossils from ∼1.0 Ga rocks in North China: Implications for a polyphyletic origin of Chuaria and a potential biological link between these two widespread Proterozoic taxa - Changtai Niu; Guangjin Li; Qing Tang; Xiaopeng Wang; Rui Huang; Hanzhi Qu; Mingyang Qiu; Bin Wan; Zhe Chen; Chuanming Zhou; Ke Pang; Xunlai Yuan (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

A tale of two vein types: Bed-parallel fibrous versus blocky filled fractures in organic-rich shales and their overpressured hydrocarbon fluids - Miao Wang; Feng Liang; Tong Lin; Yelei Wang; Hui Zhang; Qian Huang; Yifan Song; Tingting Liu; Yanwei Feng; Rui Ni; Xiaoying Guo; Tengfei Zhou; et al. (Marine and Petroleum Geology, 2024)

Structurally regulated hydrogel evaporator with excellent salt-resistance for efficient solar interfacial water evaporation - Bingxue Huang; Rui Tang; Xinmei Zheng; Gang Chen; Qingye Li; Wei Zhang; Biyou Peng (Journal of Environmental Chemical Engineering, 2024)

Experimental study on the mass burning rate and flame tilt angle of annular pool fires under cross air flow - Ping Huang; Rui Zhang; Chunxiang Liu; Xinyue Wu; Shanshan Chen; Jinhao Li; Man Li; Longxing Yu (Fuel, 2024)

Ancient terminal water treatment methods still work: Removing micropollutants in drinking water by simultaneous boiling and VUV - Jinsuo Lu; Xingxing Huang; Shiying Li; Yujie Ao; Gen Wang; Haocheng Yang; Zhiqiang Zhang; Heliang Pang; Rui Chen; Qinan Song (Chemical Engineering Journal, 2024)

In situ bioprinting of double network anti-digestive xanthan gum derived hydrogel scaffolds for the treatment of enterocutaneous fistulas - Kang Chen; Jinjian Huang; Ze Li; Jinpeng Zhang; Sicheng Li; Canwen Chen; Ye Liu; Guiwen Qu; Yitian Teng; Rui Ma; Zongan Li; Yungang Jiang; et al. (Carbohydrate Polymers, 2024)

Improving bioelectrochemical performance by sulfur-doped titanium dioxide cooperated with Zirconium based metal–organic framework (S-TiO2@MOF-808) as cathode in microbial fuel cells - Qin Qi; Guofu Huang; Rui Li; Jiale Yu; Xiaomin Chen; Zhen Liu; Yanyan Liu; Renjun Wang; Yuewei Yang; Junfeng Chen (Bioresource Technology, 2024)

Burning and plume flow behaviors of annular pool fires: with and without air entrainment through the pool center - Ping Huang; Rui Zhang; Chunxiang Liu; Xinyue Wu; Dimin Chen; Shanshan Chen; Longxing Yu (Environmental Science and Pollution Research, 2024)

Vegetation-cover control of between-site soil temperature evolution in a sandy desertland - Shuai He; Chengfu Zhang; Fan-Rui Meng; Charles P.-A. Bourque; Zhenying Huang; Xiang Li; Yalu Han; Shuang Feng; Lin Miao; Chen Liu (Science of The Total Environment, 2024)

Identification, characterization and hypolipidemic effect of novel peptides in protein hydrolysate from Protaetia brevitarsis larvae - Zong-Qi Zhang; Xin-Rui Ren; Jin Geng; Si-Cong Chen; Qing-Lei Wang; Chun-Qin Liu; Jin-Hua Xiao; Da-Wei Huang (Food Research International, 2024)

Efficient piezo-photocatalysis of Bi2O2(OH)NO3/BiOI heterojunction: Collaboration of piezoelectric polarization and interface electric field - Yuanrui Li; Xiaolei Zhang; Rui Sha; Tong Li; Cheng Hu; Shuchen Tu; Fang Chen; Hongwei Huang (Chemical Engineering Journal, 2024)

Chargeable persistent luminescence 3D-printed scaffolds: A stepwise tactic for osteosarcoma treatment - Rui Huang; Ni Ni; Yun Su; Li Gu; Yahan Ju; Dandan Zhang; Jipeng Li; Meiqi Chang; Yu Chen; Ping Gu; Xianqun Fan (Chemical Engineering Journal, 2024)

Fermentation characteristics and prebiotic potential of enzymatically synthesized butyryl-fructooligosaccharides - Zixin Yang; Diming Tan; Weiwen Chen; Jun Hu; Rui Huang; Xiyang Wu; Milen I. Georgiev; Weibin Bai; Lingmin Tian (Carbohydrate Polymers, 2024)

An observation study of the combined river discharge and sea level impact on the duration of saltwater intrusion in Pearl River estuary–Modaomen waterway - Haiju Hu; Gedun Chen; Rui Lin; Xing Huang; Zhidong Wei; Guoheng Chen (Natural Hazards, 2024)

Salmonella spvC gene suppresses macrophage/neutrophil antibacterial defense mediated by gasdermin D - Liting Zhou; Yuanyuan Li; Jiayi You; Chaoyi Wu; Lingli Zuo; Yilin Chen; Li Kang; Zhengyu Zhou; Rui Huang; Shuyan Wu (Inflammation Research, 2024)

RLP system: A single-tube two-step approach with dual amplification cascades for rapid identification of EGFR T790M - Tao Huang; Yanxi Han; Yuqing Chen; Zhenli Diao; Yu Ma; Lei Feng; Duo Wang; Rui Zhang; Jinming Li (Analytica Chimica Acta, 2024)

A chitosan-based antibacterial hydrogel with injectable and self-healing capabilities - Rui Chen; Yanan Hao; Secundo Francesco; Xiangzhao Mao; Wen-Can Huang (Marine Life Science & Technology, 2023)
The presence of bacteria directly affects wound healing. Chitosan-based hydrogel biomaterials are a solution as they offer advantages for wound-healing applications due to their strong antimicrobial properties. Here, a double-cross-linking chitosan-based hydrogel with antibacterial, self-healing, and injectable properties is reported. Thiolated chitosan was successfully prepared, and the thiolated chitosan molecules were cross-linked by Ag–S coordination to form a supramolecular hydrogel. Subsequently, the amine groups in the thiolated chitosan covalently cross-linked with genipin to further promote hydrogel formation. In vitro experimental results indicate that hydrogel can release Ag + over an extended time, achieving an antibacterial rate of over 99% against Escherichia coli and Staphylococcus aureus . Due to the reversible and dynamic feature of Ag–S coordination, an antibacterial hydrogel exhibited injectable and self-healing capabilities. Additionally, the hydrogel showed excellent biocompatibility and biodegradability.

Native ApxIIA secreted by Actinobacillus pleuropneumoniae induces apoptosis in porcine alveolar macrophages dependent on concentration and acylation - Hao Tang; Rong Wang; Siqi Pang; Weiyao Han; Qiuhong Zhang; Qiong Fang; Xiabing Chen; Qi Huang; Dexin Qiu; Rui Zhou; Lu Li (Veterinary Microbiology, 2023)

The co-regulation of the gut microbiome and host genes might play essential roles in metformin gastrointestinal intolerance - Huixiang Zhang; Jiao Lai; Lihuan Zhang; Wei Zhang; Xun Liu; Qilin Gong; Hongxi Tian; Mingzhi Yang; Tao Yang; Rui Zhao; Dongqing Li; Hehua Huang; et al. (Toxicology and Applied Pharmacology, 2023)

Increasing sensitivity of dryland water use efficiency to soil water content due to rising atmospheric CO2 - Rui Kong; Zengxin Zhang; Zejiang Yu; Richao Huang; Ying Zhang; Xi Chen; Chong-Yu Xu (Science of The Total Environment, 2023)

Accelerated aging of lithium-ion batteries: bridging battery aging analysis and operational lifetime prediction - Rui Li; Liying Bao; Lai Chen; Cheng Zha; Jingyang Dong; Nan Qi; Rui Tang; Yun Lu; Meng Wang; Rong Huang; Kang Yan; Yuefeng Su; et al. (Science Bulletin, 2023)

A bioinspired hydrogel carrier with pH/redox dual responsiveness for effective protection and intestinal targeted delivery of probiotics - Yanan Hao; Mengyuan Zhou; Rui Chen; Xiangzhao Mao; Wen-Can Huang (Journal of Food Engineering, 2023)

Micromechanics-based model of rock considering compaction deformation: Analysis of microcrack influence from discrete and continuous perspectives - Huiguan Chen; Cheng Zhao; Rui Zhang; Lin Huang; Haoyu Pan; Yuan Qian; Hongwei Yang (Computers and Geotechnics, 2023)

Spatial bandgap tailoring via a novel injection chemical bath deposition enables highly efficient carbon-based Sb2(S,Se)3 thin film solar cells - Peng Tang; Zi-Heng Huang; You-Xian Chen; Hu Li; Li-Quan Yao; Hui Li; Li-Mei Lin; Jin-Rui Cai; Ya-Lu Zhan; Dong Wei; Shui-Yuan Chen; Da-Qin Chen; et al. (Chemical Engineering Journal, 2023)

Serum HBV RNA levels among untreated adults with chronic hepatitis B in distinct immune phases and liver histopathology statuses - Qin Xu; Hai Ding; Tao Bai; Rui Huang; Jian Wang; Jun Zhang; Hewei Luan; Jun Wang; Yue Yang; Yuxin Chen (Journal of Molecular Histology, 2023)

Mitochondrial dysfunction: a new molecular mechanism of intervertebral disc degeneration - Chao Song; Yulin Xu; Qinghua Peng; Rui Chen; Daqian Zhou; Kang Cheng; Weiye Cai; Tao Liu; Chenyi Huang; Zhijiang Fu; Cong Wei; Zongchao Liu (Inflammation Research, 2023)

The predictive, preventive, and personalized medicine of insomnia: gut microbiota and inflammation - Hao-Wen Chen; Rui Zhou; Bi-Fei Cao; Kuan Liu; Qi Zhong; Yi-Ning Huang; Hua-Min Liu; Jin-Qing Zhao; Xian-Bo Wu (EPMA Journal, 2023)

Enhanced As extraction from paddy soils with high As contamination risk by rice plant upon Si fertilization - Rui Huang; Xin Wang; Wei Wei; Yunhe Xie; Saihua Liu; Haoyu Chen; Renjie Zhang; Xionghui Ji (Chemosphere, 2023)

The mechanism of DEHP degradation by the combined action of biochar and Arthrobacter sp. JQ-1: Mechanisms insight from bacteria viability, degradation efficiency and changes in extracellular environment - Rui Guan; Lei Wang; Ying Zhao; Fuxin Huang; Ying Zhang; Xiaodong Wang; Yuxin Chen; Mingze Li; Didi Wang (Chemosphere, 2023)

Sensory-directed isolation and identification of an intense salicin-like bitter compound in infected teas with bird’s eye spot disease - Jingna Yan; Yiwen Miao; Jingyun Zhou; Rui Huang; Hongwei Dai; Ming Liu; Yunzhi Lin; Yingjuan Chen; Chi-Tang Ho; Huarong Tong; Qing Meng (Food Research International, 2023)

Portable multichannel detection instrument based on time-resolved fluorescence immunochromatographic test strip for on-site detecting pesticide residues in vegetables - Rui Xu; Yaodong Xiang; Zheng Shen; Gaozhen Li; Jiashuai Sun; Peiyu Lin; Xiaofeng Chen; Jingcheng Huang; Haowei Dong; Zhenying He; Wenzheng Liu; Lu Zhang; et al. (Analytica Chimica Acta, 2023)

Tonian discoidal fossils from North China: Relating discs to worm-like annulated tubes and their paleoecological and evolutionary implications - Guangjin Li; Ke Pang; Qing Tang; Lei Chen; Chengxi Wu; Rui Huang; Bin Wan; Xunlai Yuan; Chuanming Zhou (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Bimodal interferences of Pb(II) induced by parallel deposition in Pb(II)-Cu(II) electrochemical detections: Voltammetric signals analysis combined with numerical simulations on transient interfacial phenomena - Rui-Ze Xia; Xin Cai; Bo Liang; Hai-Hua Dai; Yang-Zhi Liu; Meng Yang; Shi-Hua Chen; Pei-Hua Li; Xing-Jiu Huang (Journal of Hazardous Materials, 2023)

Surface modification of PVDF membranes with quaternized chitosan for selective separation of negatively charged polysaccharides – exemplified with heparin - Rui Zhang; Yahong Li; Jingjing Yan; Jianxian Zeng; Yuan Liu; Mingming Zhang; Pengfei Liu; Xiaoping Huang; Erdong Zhang; Kaipeng Cheng; Jingyu Chen; Jialin Sun (Journal of Environmental Chemical Engineering, 2023)

Polyamide/UiO-66-NH2 nanocomposite membranes by polyphenol interfacial engineering for molybdenum(VI) removal - Zhenwei Wu; Jianxian Zeng; Zhengqiu Yuan; Rui Zhang; Xiaoping Huang; Fan Feng; Minjuan Chen; Kai Jin; Shengkai Yang; Yahong Li (Desalination, 2023)

Microwave-coordinated KOH directionally modulated N/O co-doped porous biochar from Enteromorpha and its structure–effect relationships in efficient CO2 capture - Juan Luo; Yi Chen; Huimin Huang; Rui Ma; Ning Ma; Feng Yan; Jiyun Xu; Junshen Zhang; Jiashan Chen; Shichang Sun (Chemical Engineering Journal, 2023)

Enhanced nitrate removal by alcohol-involved nitrate photolysis-induced advanced reduction process - Yawei Xie; Shiyi Ni; Shiming Wang; Chenda Wu; Keqi Huang; Dehua Ma; Lujun Chen; Rui Liu; Hongyuan Liu (Chemical Engineering Journal, 2023)

Bradykinin-pretreated Human cardiac-specific c-kit+ Cells Enhance Exosomal miR-3059-5p and Promote Angiogenesis Against Hindlimb Ischemia in mice - Jingzhou Li; Fei Song; Ruolan Chen; Jinjuan Yang; Jie Liu; Li Huang; Fuyu Duan; Meng Kou; Boon Xuan Lian; Xiaoxia Zhou; Weimin Han; Liang Mao; et al. (Stem Cell Reviews and Reports, 2023)

Revealing the solid-solution interface interference behaviors between Cu2+ and As(III) via partial peak area analysis of simulations and experiments - Bo Liang; Xiang-Yu Xiao; Zong-Yin Song; Yong-Yu Li; Xin Cai; Rui-Ze Xia; Shi-Hua Chen; Meng Yang; Pei-Hua Li; Chu-Hong Lin; Xing-Jiu Huang (Analytica Chimica Acta, 2023)

Thermal analysis technology to utilize waste biomass and waste heat to produce high-quality combustible gas through simulations and experiments - Weiming Song; Xiaoqing Chen; Yifeng Huang; Rui Jiang; Jianan Zhou (Science of The Total Environment, 2023)

Rare loss-of-function variants reveal threshold and multifactorial inheritance of dextrocardia - Zhongzhong Chen; Yunqian Gao; Lei Lu; Nan Li; Pei Liu; Rui Peng; Lingling Liu; Hefeng Huang; Qihua Fu; Haifa Hong; Jianguo Zhang; Hongyan Wang (Science Bulletin, 2023)

Collaborative removal of fine catalysts particles and insoluble organics from methanol-to-olefins reaction wastewater using horizontal swirl regeneration micro-channel separation (HSRMS) - Jianqi Chen; Rui Cai; Haitao Huang; Qi Wei; Bing Liu; Aosong Wei; Meng Zhang; Wenjie Lv; Hualin Wang (Process Safety and Environmental Protection, 2023)

Lipid droplets proteome reveals dynamic changes of lipid droplets protein during embryonic development of Carya cathayensis nuts - Anjing Chen; Shuai Hu; Dongmei Zhu; Rui Zhao; Chunying Huang; Yanli Gao (Plant Science, 2023)

Integrated insight into the molecular mechanisms of selenium-modulated, MPP+-induced cytotoxicity in a Parkinson’s disease model - Wen Liu; Feiyang Zhang; Wu Liang; Kaixin Huang; Chenguang Jia; Jie Zhang; Xiang Li; Wei Wei; Rui Gong; Jincao Chen (Journal of Trace Elements in Medicine and Biology, 2023)

Anaerobic selenite-reducing bacteria and their metabolic potentials in Se-rich sediment revealed by the combination of DNA-stable isotope probing, metagenomic binning, and metatranscriptomics - Rui Xu; Max Kolton; Wan Tao; Xiaoxu Sun; Pingzhou Su; Duanyi Huang; Miaomiao Zhang; Zhaohui Yang; Zhaohui Guo; Hanbing Gao; Qi Wang; Baoqin Li; et al. (Journal of Hazardous Materials, 2023)

Preparation and emulsification properties of cationic starch-xanthan gum composite nanoparticles - Wei Zhou; Zhen Cai; Rui Zhang; Kun Hu; Fangfang Wu; Yong Hu; Chao Huang; Yun Chen (Food Chemistry, 2023)

Enzymatic synthesis of propionyl-fructooligosaccharides and their evaluation as a gut microbiota modulator - Diming Tan; Weiwen Chen; Zixin Yang; Minjing Rong; Rui Huang; Xiyang Wu; Weibin Bai; Lingmin Tian (Food Hydrocolloids, 2023)

Cooperated catalytic mechanism of atomically dispersed binary Cu-N4 and Zn-N4 in N-doped carbon materials for promoting electrocatalytic CO2 reduction to CH4 - Cuihua An; Shuai Wu; Rui Huang; Xiaodong Chen; Xiaopeng Han; Hassanien Gomaa; Qibo Deng; Libin Zhao; Ning Hu (Chemical Engineering Journal, 2023)

Functional characterization of novel NPRL3 mutations identified in three families with focal epilepsy - Shiyue Du; Sheng Zeng; Li Song; Hongying Ma; Rui Chen; Junyu Luo; Xu Wang; Tingbin Ma; Xuan Xu; Hao Sun; Ping Yi; Jifeng Guo; et al. (Science China Life Sciences, 2023)

Nafamostat mesilate prevented caerulein-induced pancreatic injury by targeting HDAC6-mediated NLRP3 inflammasome activation - Peng Chen; Li-Jun Zhao; Ling Huang; Wen-Qi He; Ying-Rui Tang; Yi Liu; Jian-Dong Ren (Inflammation Research, 2023)

Purification of conchocelis of Neoporphyra haitanensis by the method of dominant Bacteria enrichment comprehensive treatment - Mingjie Ma; Qiqin Liu; Lin Huang; Peng Zhang; Haimin Chen; Juanjuan Chen; Qijun Luo; Tiegan Wang; Rui Yang (Aquaculture, 2023)

Overexpression of CdtCIPK21 from triploid bermudagrass reduces salt and drought tolerance but increases chilling tolerance in transgenic rice - Rui Liu; Shilian Huang; Anyao Huang; Miao Chen; Yurong Luo; Zhenfei Guo; Shaoyun Lu (Journal of Plant Physiology, 2023)

Different dietary fibers unequally remodel gut microbiota and charge up anti-obesity effects - Jia-Jia Wen; Ming-Zhi Li; Jie-Lun Hu; Jiang Wang; Zhi-Qiang Wang; Chun-Hua Chen; Jing-Rui Yang; Xiao-Jun Huang; Ming-Yong Xie; Shao-Ping Nie (Food Hydrocolloids, 2023)

Correction to: Mitochondrial Hydrogen Peroxide Activates PTEN and Inactivates Akt Leading to Autophagy Inhibition-Dependent Cell Death in Neuronal Models of Parkinson’s Disease - Qianyun Yu; Ruijie Zhang; Tianjing Li; Liu Yang; Zhihan Zhou; Long Hou; Wen Wu; Rui Zhao; Xiaoling Chen; Yajie Yao; Shile Huang; Long Chen (Molecular Neurobiology, 2023)

Whole-plant foods and their macromolecules: untapped approaches to modulate neuroinflammation in Alzheimer’s disease - Rui Huang; Zhenjun Zhu; Qingping Wu; Alaa El-Din Ahmed Bekhit; Shujian Wu; Mengfei Chen; Juan Wang; Yu Ding (Critical Reviews in Food Science and Nutrition, 2023)

Pollution concerns in mariculture water and cultured economical bivalves: Occurrence of microplastics under different aquaculture modes - Kexin Song; Rui Wang; Guang Yang; Siqi Xie; Yangjun Chen; Feifei Yang; Wei Huang; Tao Zhang; Zhihua Feng (Journal of Cleaner Production, 2023)

Microwave-induced preparation of MgO-loaded N-rich porous biochar from marine biomass for efficient CO2 capture and mechanism exploration via theoretical calculation - Juan Luo; Yi Chen; Xi Zhang; Rui Ma; Huimin Huang; Shichang Sun; Junhao Lin; Feng Yan; Jiyun Xu (Journal of Cleaner Production, 2023)

Highly synergistic and polarized KNbO3/WO3 heterojunction for piezo-photocatalytic degradation of organic pollutant - Rui Huang; Wei Cai; Heng Zhang; Zhenhua Wang; Qin Zhang; Rongli Gao; Gang Chen; Xiaoling Deng; Xiang Lei; Jiling Dong; Xiaoyan Liu; Chunlin Fu (Journal of Environmental Chemical Engineering, 2023)

Screening of goaty flavor-inhibiting lactic acid bacteria and their effects on the flavor profiles of goat milk cakes - Huaixiang Tian; Rui Yang; Xuefeng Sun; Haiyan Yu; Juan Huang; Haibin Yuan; Xinman Lou; Zhaohu Yuan; Chen Chen (Food Bioscience, 2023)

Mitochondrial Hydrogen Peroxide Activates PTEN and Inactivates Akt Leading to Autophagy Inhibition-Dependent Cell Death in Neuronal Models of Parkinson’s Disease - Qianyun Yu; Ruijie Zhang; Tianjing Li; Liu Yang; Zhihan Zhou; Long Hou; Wen Wu; Rui Zhao; Xiaoling Chen; Yajie Yao; Shile Huang; Long Chen (Molecular Neurobiology, 2023)

Underestimation of biomass burning contribution to PM2.5 due to its chemical degradation based on hourly measurements of organic tracers: A case study in the Yangtze River Delta (YRD) region, China - Qing Li; Kun Zhang; Rui Li; Liumei Yang; Yanan Yi; Zhiqiang Liu; Xiaojuan Zhang; Jialiang Feng; Qiongqiong Wang; Wu Wang; Ling Huang; Yangjun Wang; et al. (Science of The Total Environment, 2023)

A quasi-one-dimensional bulk thermoelectrics with high performance near room temperature - Qingxin Dong; Junsen Xiang; Zhen Wang; Yunxiu Li; Rui Lu; Te Zhang; Nan Chen; Yifei Huang; Yiyan Wang; Wenliang Zhu; Guodong Li; Huaizhou Zhao; et al. (Science Bulletin, 2023)

Clinical significance of fractional anisotropy in cerebral white matter regional vulnerability caused by carbon monoxide poisoning: A systematic review and meta-analysis - Wen-Chiu Hsiao; Rui Nouchi; Hsin-I Chang; Shih-Wei Hsu; Chen-Chang Lee; Shu-Hua Huang; Chi-Wei Huang; Chiung-Chih Chang; Chia-Hsiung Cheng (NeuroToxicology, 2023)

Photo-assisted thermal catalysis for methanol synthesis from methane oxidation on Cu-MOR/g-C3N4 - Yan-Qun Chen; Rui-Xin Zhang; Miao Ren; Ya-Xin Jin; Wen-Jing Wang; Jia-Yao Feng; Zhi-Hua Gao; Zhi-Feng Yan; Yi-Ming Liu; Wei Huang; Lei Liu; Zhi-Jun Zuo (Fuel, 2023)

Ciprofloxacin degradation performances and mechanisms by the heterogeneous electro-Fenton with flocculated fermentation biochar - Yanchao Jin; Peiwen Huang; Xiongjian Chen; Li-Ping Li; Chun-Yan Lin; Xiao Chen; Rui Ding; Jianxi Liu; Riyao Chen (Environmental Pollution, 2023)

Study on the effect of different concentrations of choline glycine ionic liquid-water mixtures on debranched starch butyrylation reaction - Xi Zhang; Yi Chen; Rui Huang; Jinsheng Zhang; Chunhong Xiong; Ganhui Huang (Carbohydrate Polymers, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Pegmatite magmatic evolution and rare metal mineralization of the Dahongliutan pegmatite field, Western Kunlun Orogen: Constraints from the B isotopic composition and mineral-chemistry - Rui Cao; Yongbao Gao; Bin Chen; Leon Bagas; Shengchao Yan; Chao Huang; Hui Zhao (International Geology Review, 2023)

Assessing the effects of short-term traffic restriction policies on traffic-related air pollutants - Xiao-Rui Fang; Xing-Hang Zhu; Xing-Zhou Li; Zhong-Ren Peng; Hu Qingyao; Hong-Di He; AJ Yuan Chen; Huang Cheng (Science of The Total Environment, 2023)

Extreme cooling of 12.5 °C triggered by Typhoon Fungwong (2008) - Zhe-Wen Zheng; Jia-Yi Lin; Ganesh Gopalakrishnan; Yi-Rui Chen; Doon-Jing Doong; Chung-Ru Ho; Quanan Zheng; Chau-Ron Wu; Chen-Fen Huang (Ocean Modelling, 2023)

Multi-model analysis of historical runoff changes in the Lancang-Mekong River Basin – Characteristics and uncertainties - Yuxin Li; Aifang Chen; Ganquan Mao; Penghan Chen; Hao Huang; Hong Yang; Zifeng Wang; Kai Wang; He Chen; Ying Meng; Rui Zhong; Pengfei Wang; et al. (Journal of Hydrology, 2023)

Efficient removal of Cr(VI) by the modified biochar with chitosan schiff base and MnFe2O4 nanoparticles: Adsorption and mechanism analysis - Ling Yan; Weijuan Guo; Binbin Huang; Yujun Chen; Xinyu Ren; Yiyang Shen; Yefeng Zhou; Rui Cheng; Jie Zhang; Muqing Qiu; Baowei Hu (Journal of Environmental Chemical Engineering, 2023)

Amorphous nanophosphates of dual-metal (Co and Ni) for the decomposition of ozone under humid conditions - Qian Zhang; Jifei Liao; Guangzhi Du; Yu Lin; Xiaoqiong Liu; Rui Wang; Lingyu Huang; Wenyan Xiao; Jiahao Chen; Yan Fu (Journal of Environmental Chemical Engineering, 2023)

Long-term exposure to fine particulate matter and site-specific cancer mortality: A difference-in-differences analysis in Jiangsu province, China - Zhaoyu Fan; Yingxin Li; Jing Wei; Gongbo Chen; Rui Wang; Ruijun Xu; Tingting Liu; Ziquan Lv; Suli Huang; Hong Sun; Yuewei Liu (Environmental Research, 2023)

Preparation of high performance porous carbon by microwave synergistic nitrogen/phosphorus doping for efficient removal of Cu2+ via capacitive deionization - Huimin Huang; Yi Chen; Rui Ma; Juan Luo; Shichang Sun; Junhao Lin; Yanyi Wang (Environmental Research, 2023)

C3-symmetric trimeric imidazole naphthoquinone derivative with dual redox-active sites for high-performance cathodic lithium storage - Yifang Zhu; Wei Jin; Haiguang Gao; Yanli Chen; Tai-Rui Wu; De-Yin Wu; Yucheng Huang; Dengfeng Guo; Zhidong Chen; Qinghong Huang; Jianyu Cao; Juan Xu (Chemical Engineering Journal, 2023)

π-Conjugated N-heterocyclic compound with redox-active quinone and pyrazine moieties as a high-capacity organic cathode for aqueous zinc-ion batteries - Yanjun Shi; Pengcheng Wang; Haiguang Gao; Wei Jin; Yanli Chen; Yucheng Huang; Tai-Rui Wu; De-Yin Wu; Juan Xu; Jianyu Cao (Chemical Engineering Journal, 2023)

Transcriptomic analysis of juvenile cobia in response to hypoxic stress - Jian-Sheng Huang; Zhi-Xiong Guo; Jian-Dong Zhang; Wei-Zheng Wang; Zhong-Liang Wang; Rui-Tao Xie; Eric Amenyogbe; Gang Chen (Aquaculture International, 2023)

Modelling air conductivity function of unsaturated root-permeated soil - Rui Chen; Jun-Wen Huang; Anthony Kwan Leung; Zhong-Kui Chen; Yang Ping; Ying Xu (Soil and Tillage Research, 2023)

Pyrolysis temperature affects the physiochemical characteristics of lanthanum-modified biochar derived from orange peels: Insights into the mechanisms of tetracycline adsorption by spectroscopic analysis and theoretical calculations - Zhihao Chen; Bingfeng Lin; Yingping Huang; Yanbiao Liu; Yonghong Wu; Rui Qu; Cilai Tang (Science of The Total Environment, 2023)

Tea polyphenol and epigallocatechin gallate ameliorate hyperlipidemia via regulating liver metabolism and remodeling gut microbiota - Jia-Jia Wen; Ming-Zhi Li; Chun-Hua Chen; Tao Hong; Jing-Rui Yang; Xiao-Jun Huang; Fang Geng; Jie-Lun Hu; Shao-Ping Nie (Food Chemistry, 2023)

Molecular characterization of a teleost-specific toll-like receptor 22 (tlr22) gene from yellow catfish (Pelteobagrus fulvidraco) and its transcriptional change in response to poly I:C and Aeromonas hydrophila stimuli - Xiu-Ying Wei; Jun Wang; Sheng-Tao Guo; Yun-Yun Lv; Yan-Ping Li; Chuan-Jie Qin; Yuan-Chao Zou; Qing-Chao Shi; Peng Hu; Xiao-Qin Xiong; Yang He; Rui Li; et al. (Fish & Shellfish Immunology, 2023)

Nuclides selection method for nuclear reactor shielding based on non-dominated sorting - Rui Li; Shichang Liu; Xian Zhang; Chai Xiaoming; Yang Junyun; Huang Qianming; Yixue Chen (Annals of Nuclear Energy, 2023)

Climate change has increased the global threats posed by three ragweeds (Ambrosia L.) in the Anthropocene - Xiaoqing Xian; Haoxiang Zhao; Rui Wang; Hongkun Huang; Baoxiong Chen; Guifen Zhang; Wanxue Liu; Fanghao Wan (Science of The Total Environment, 2023)

Fabrication of gelatin-EGCG-pectin ternary complex stabilized W/O/W double emulsions by ultrasonic emulsification: Physicochemical stability, rheological properties and structure - Xiang Huang; Rui Tu; Hongbo Song; Kai Dong; Fang Geng; Lei Chen; Qun Huang; Yingmei Wu (Journal of Food Engineering, 2023)

Rapid nitrification using nitrifying biomass acclimated to sulfamethoxazole (SMX) - Xinyue Zhang; Jiayu Huang; Song Chen; Ning Yan; Rui Liu; Yongming Zhang; Bruce E. Rittmann (Journal of Environmental Chemical Engineering, 2023)

Facilitating both anionic and cationic redox processes in Na-rich layered cathode materials by heteroatomic doping - Ziwei Chen; Maolin Yang; Zhongyuan Huang; Yanda Fu; Zhefeng Chen; Simo Li; Minzhi zhan; Rui Wang; Mihai Chu; Rui Qi; Xing Cheng; Zhewen Ma; et al. (Chemical Engineering Journal, 2023)

Redox of anionic and cationic radical intermediates in a bipolar polyimide COF for high-performance dual-ion organic batteries - Shuai Gu; Jingjing Chen; Rui Hao; Xi Chen; Zhiqiang Wang; Iftikhar Hussain; Guiyu Liu; Kun Liu; Qingmeng Gan; Zhiqiang Li; Hao Guo; Yingzhi Li; et al. (Chemical Engineering Journal, 2023)

Endothelial LRP1-ICD Accelerates Cognition-Associated Alpha-Synuclein Pathology and Neurodegeneration through PARP1 Activation in a Mouse Model of Parkinson’s Disease - Rui Huang; Yuyuan Gao; Qingrui Duan; Qingxi Zhang; Peikun He; Jianing Chen; Guixian Ma; Limin Wang; Yuhu Zhang; Kun Nie; Lijuan Wang (Molecular Neurobiology, 2023)

Evaluation of the pathogenesis of non-typical strain with α-hemolysin, Vibrio parahaemolyticus 353, isolated from Chinese seafood through comparative genome and transcriptome analysis - Fei Zha; Rui Pang; Shixuan Huang; Jumei Zhang; Juan Wang; Moutong Chen; Liang Xue; Qinghua Ye; Shi Wu; Meiyan Yang; Qihui Gu; Yu Ding; et al. (Marine Pollution Bulletin, 2023)

Synergistic activation of anionic redox via cosubstitution to construct high-capacity layered oxide cathode materials for sodium-ion batteries - Haocheng Ji; Wenhai Ji; Haoyu Xue; Guojie Chen; Rui Qi; Zhongyuan Huang; Hui Fang; Mihai Chu; Lele Liu; Zhewen Ma; Shenyang Xu; Jingjun Zhai; et al. (Science Bulletin, 2023)

Impact of international trade on water scarcity: An assessment by improving the Falkenmark indicator - Rui Zhong; Aifang Chen; Dandan Zhao; Ganquan Mao; Xu Zhao; Hao Huang; Junguo Liu (Journal of Cleaner Production, 2023)

Chemical composition, sources and evolution of PM2.5 during wintertime in the city cluster of southern Sichuan, China - Junke Zhang; Xiaojuan Huang; Jiaqi Li; Luyao Chen; Rui Zhao; Rui Wang; Wei Sun; Chunying Chen; Yunfei Su; Fangzheng Wang; Yawen Huang; Chaobiao Lin (Atmospheric Pollution Research, 2023)

Plant-associated Microbe System in Treatment of Heavy Metals–contaminated Soil: Mechanisms and Applications - Zhiming Ren; Rui Cheng; Peng Chen; Yuanyuan Xue; Hong Xu; Yao Yin; Guangtuan Huang; Wei Zhang; Lehua Zhang (Water, Air, & Soil Pollution, 2023)

Receptor and Ionic Mechanism of Histamine on Mouse Dorsolateral Striatal Neurons - Jian-Ya Peng; Kang-Li Shen; Xiu-Juan Fan; Zeng-Xin Qi; Hui-Wei Huang; Jian-Lan Jiang; Jian-Hua Lu; Xiao-Qin Wang; Xiao-Xia Fang; Wang-Rui Yuan; Qiao-Xuan Deng; Shu Chen; et al. (Molecular Neurobiology, 2023)

Evaluating the effects of contact time and leaching solution on measured solubilities of aerosol trace metals - Rui Li; Shuwei Dong; Chengpeng Huang; Feng Yu; Fu Wang; Xiaofei Li; Huanhuan Zhang; Yan Ren; Mingxian Guo; Qingcai Chen; Baozhu Ge; Mingjin Tang (Applied Geochemistry, 2023)

Solar ring mission: Building a panorama of the Sun and inner-heliosphere - Yuming Wang; Xianyong Bai; Changyong Chen; Linjie Chen; Xin Cheng; Lei Deng; Linhua Deng; Yuanyong Deng; Li Feng; Tingyu Gou; Jingnan Guo; Yang Guo; et al. (Advances in Space Research, 2023)

Effects of different growth patterns of Tamarix chinensis on saline-alkali soil: implications for coastal restoration and management - Chen Gu; Weibin Huang; Qing Shao; Jiyan Shi; Jianliang Rui; Yanming Yu; Zhinai Lu; Yao Chen; Xiaojun Chen; Shudi Dong; Chenghua Ye; Ya Tuo (Biotechnology Letters, 2022)

Halophyte Vegetation Influences Soil Microbial Community of Coastal Salt Marsh - Chen Gu; Jiyan Shi; Jianliang Rui; Yanming Yu; Weibin Huang; Zhinai Lu; Yao Chen; Xiaojun Chen; Shudi Dong; Zhijun Hu; Chenghua Ye (Journal of Ocean University of China, 2022)

Sensor Partitioning Placements via Random Walk and Water Quality and Leakage Detection Models within Water Distribution Systems - Tianwei Mu; Manhong Huang; Shi Tang; Rui Zhang; Gang Chen; Baiyi Jiang (Water Resources Management, 2022)

Characterizing diversity based on phenotypes and molecular marker analyses of purple yam (Dioscorea alata L.) germplasm in southern China - Xin Chen; Jingyu Sun; Qianglong Zhu; Yao Xiao; Hongyu Zhang; Yingjin Huang; Putao Wang; Tianxu Cao; Rui Hu; Zijin Xiang; Nan Shan; Qinghong Zhou (Genetic Resources and Crop Evolution, 2022)

Effect of winter feeding frequency on growth performance, biochemical blood parameters, oxidative stress, and appetite-related genes in Takifugu rubripes - Xiaoqiang Gao; Xinyi Wang; Xi Wang; Hongxu Li; Liang Xu; Yingying Fang; Shuquan Cao; Bin Huang; Haibin Chen; Rui Xing; Baoliang Liu (Fish Physiology and Biochemistry, 2022)

Genome-wide analysis of Keratinibaculum paraultunense strain KD-1 T and its key genes and metabolic pathways involved in the anaerobic degradation of feather keratin - Weidong Wu; Shichun Ma; Rui Chen; Yan Huang; Yu Deng (Archives of Microbiology, 2022)

Changes in amino acid and fatty acid composition during early development in cobia (Rachycentron canadum) - Jian-sheng Huang; Rong-xin Li; Rui-tao Xie; You-ming Chen; Jian-dong Zhang; Eric Amenyogbe; Gang Chen (Frontiers in Marine Science, 2022)
An estimation of the utilization of endogenous nutrients from the yolk sac that occurs during embryonic and early larval development can be a valuable approach to studying the nutritional requirements of fish larvae. In this study, fertilized eggs, embryos (before the membrane, 24 hours after fertilization), newly-hatched larvae (0-d-old), and open-mouthed larvae (3-day-old, unfed rotifers) samples of cobia ( Rachycentron canadum ) were collected to determine the amino acid and fatty acid profiles. Crude protein composition varies significantly for cobia during the different stages of development. The total amino acids, except for lysine(Lys), histidine (His), methionine(Met), serine(Ser), and glycine(Gly), had no significant change in the early development stage ( P > 0.05); the content of other six essential amino acids (EAA) and six non-essential amino acids (NEAA) was consistent with the changing trend of total essential amino acid. From hatching newly hatched larvae to open-mouthed larvae, except for Leu, Phe and Ser, decreased significantly ( P <0.05). From the utilization rate of FAA, the utilization rate of Lys and Leu was the highest (60.26%) and (52.21%) in the embryonic and endogenous nutritional stages, respectively. The water content of the open-mouthed larvae of cobia was significantly higher than that of the fertilized eggs, embryos, and newly hatched larvae ( P < 0.05). Three kinds of saturated fatty acids (SFA), five kinds of monounsaturated fatty acids (MUFA), and eight kinds of polyunsaturated fatty acids (PUFA) were detected in the dry samples of each developmental stage. Based on these results, juvenile cobia can thrive with a wide range of crude protein concentrations. Further refinement of commercial cobia production feeds would have beneficial consequences for economic and environmental concerns due to the positive impacts of optimizing the protein component as well as the ability to maintain the rapid growth rates. The results show that the larval development of cobia needs to consume large amounts of n3PUFA (especially DHA and EPA) to improve the larvae’s survival rate. Research methods will always have limitations when evaluating the relationship between early life nutrition interventions and well-being outcomes later in life. This study provides essential information regarding cobia larvae’s fatty acid requirements.

Heavy metal pollution status and deposition history of mangrove sediments in Zhanjiang Bay, China - Daobin Tang; Songying Luo; Suyan Deng; Rui Huang; Bishan Chen; Ziyi Deng (Frontiers in Marine Science, 2022)
Mangroves have high ecological service value and play an important role in achieving carbon neutrality. However, the ecological services provided by mangroves are gradually declining due to the threat of various pollutants, especially heavy metal (HM) pollution. Researching the status and history of heavy metals (HMs) in mangrove sediments improves understanding of how mangroves can be protected. We studied the Zhanjiang Bay mangroves, which is an important part of the Zhanjiang Mangrove National Nature Reserve, and is greatly affected by human activities, as an example. We analyzed the pollution levels and deposition process of HMs and their influencing factors. In the mangrove surface sediments of Zhanjiang Bay, Pb, Cr, and Co were slightly to moderate enriched and Cu was moderate-heavy enriched. Zn and Hg showed moderate-heavy enrichment and heavy enrichment, respectively. Cu, Zn, Hg, and Co were 1.5, 1.88, 2.66, and 1.27 times the local background, respectively. Cu, Zn, and Hg mainly originated from anthropogenic sources, and Co may have derived from natural sources. The HM data of mangrove sedimentary cores in Zhanjiang Bay were obtained for the first time; high HM content appeared in the deep layer of the cores but not in the mangrove surface sediments. Both cores were well documented for the effects of natural and anthropogenic factors on the deposition process of HMs. Among them, the high enrichment of Hg in 1909–1921 may be closely related to human activities rather than natural formation. Before 1954, dense mangroves favored the accumulation and gradual increase of HMs. The intense human activity in 1945–1963 during the period of economic construction and reclamation of the Nansan Island Engineering led to significant increases in Cu, Zn, Pb, Cr, and Co, which reached their highest values in more than one hundred years. After 1963, anthropic factors such as deforestation and conversion to aquaculture sharply reduced mangrove area. Reclamation engineering enhanced tidal erosion. Natural factors such as precipitation, storm surge, sea-level rise, and high tides have accelerated the erosion and dilution of mangrove sediments in Zhanjiang Bay. These factors have led to the gradual reduction of HM content in sedimentary cores.

Molecular Characterization and Expression Analysis of Glutaredoxin 5 in Black Tiger Shrimp (Penaeus monodon) and Correlation Analysis Between the SNPs of PmGrx5 and Ammonia-N Stress Tolerance Trait - Rui Fan; Shigui Jiang; Yundong Li; Qibin Yang; Song Jiang; Jianhua Huang; Lishi Yang; Xu Chen; Falin Zhou (Frontiers in Marine Science, 2022)
Glutaredoxins (Grxs) are glutathione-dependent oxidoreductases that belong to the thioredoxin (Trx) superfamily and are an essential part of the redox system in living organisms. However, there is a serious lack of sequence information and functional validation associated with Grxs in crustaceans. In this study, a new Grx gene ( PmGrx5 ) was identified and characterized in black tiger shrimp ( Penaeus monodon ). The full-length cDNA of PmGrx5 is 787 bp and consists of 114 bp 5′-UTR, 232 bp 3′-UTR, and 441 bp ORF, encoding a hypothetical protein of 146 amino acids. The putative PmGrx5 protein is 16.27 kDa with a theoretical isoelectric point of 5.90. Sequence alignment showed that PmGrx5 had the highest amino acid sequence homology with Grx5 from Penaeus vannamei at 98.63% and clustered with Grx5 from other crustaceans. Quantitative real-time PCR (qRT-PCR) analysis showed that PmGrx5 was expressed in all tissues examined, with a higher expression in the testis, stomach, lymphoid organ, and gill. PmGrx5 was continuously expressed during development, with the highest expression in zoea I. Ammonia-N stress and bacterial infection both differentially upregulated PmGrx5 expression in the hepatopancreas and gill. In addition, when PmGrx5 was inhibited, the expression of some other antioxidant enzymes was upregulated at the beginning of ammonia-N stress, but as the stress time increased, the expression of antioxidant enzymes was inhibited, the expression of apoptotic genes was increased, and the GSH content was significantly reduced. Inhibition of PmGrx5 led to a greater risk of oxidative damage in shrimp. In addition, the relationship between SNPs in exons of the PmGrx5 gene and tolerance to ammonia-N stress was identified and analysed. A total of nine SNPs were successfully identified, eight of which were significantly associated with ammonia and nitrogen stress tolerance trait in shrimp ( P < 0.05). The present study shows that PmGrx5 is involved in redox regulation and plays an important role in shrimp resistance to marine environmental stresses. Meanwhile, this study will provide a basis for molecular marker breeding in shrimp.

Laboratory and centrifugal model tests on failure mechanism of canal slopes under cyclic action of wetting–drying - Rui Zhu; Ying-hao Huang; Chen Zhang; Wan-li Guo; Hao Chen (European Journal of Environmental and Civil Engineering, 2022)

Dynamics of seasonal and interannual variability of the ocean bottom pressure in the Southern Ocean - Xiaoqin Xiong; Xuhua Cheng; Niansen Ou; Tao Feng; Jianhuang Qin; Xiao Chen; Rui Xin Huang (Acta Oceanologica Sinica, 2022)

Study on excavation stability of shallow rectangular shield pipe jacking tunnel - Wantao Ding; Zhongrong Wang; Xinghang Huang; Rui Chen; Lewen Zhang; Yingjie Zheng; Xiaowei Guo (Arabian Journal of Geosciences, 2022)

Face failure mechanism of shield tunnel in sandy ground with different low moisture contents - Zhongrong Wang; Wantao Ding; Xinghang Huang; Rui Chen; Keqi Liu (Arabian Journal of Geosciences, 2022)

Vision technique for deflection measurements based on laser positioning - Guojun Wang; Yaxin Huang; Qilin Zhao; Liang Chen; Ting Rui; Dongdong Zhang (European Journal of Environmental and Civil Engineering, 2022)

Geochemical and Sr–Nd–Li isotopic constraints on the genesis of the Jiajika Li-rich pegmatites, eastern Tibetan Plateau: implications for Li mineralization - Hui Zhao; Bin Chen; Chao Huang; Chuang Bao; Qian Yang; Rui Cao (Contributions to Mineralogy and Petrology, 2022)

Sigma-1 Receptor Activation Suppresses Microglia M1 Polarization via Regulating Endoplasmic Reticulum–Mitochondria Contact and Mitochondrial Functions in Stress-Induced Hypertension Rats - Kokwin Ooi; Li Hu; Yi Feng; Chenzhi Han; Xiaorong Ren; Xinyi Qian; Haofeng Huang; Sijia Chen; Qi Shi; Hong Lin; Jijiang Wang; Danian Zhu; et al. (Molecular Neurobiology, 2021)

The transcribed ultraconserved element uc.51 promotes the proliferation and metastasis of breast cancer by stabilizing NONO - Xiaoqing Shi; Xiaofeng Huang; Rui Chen; Yan Li; Yinggang Xu; Weiwei Zhang; Qiannan Zhu; Xiaoming Zha; Jue Wang (Clinical & Experimental Metastasis, 2021)

Correction to: Temporal and spatial evolution patterns of drought in China over the past 500 years - Cuixia Wei; Bing Guo; Wenqian Zang; Fei Yang; Yuefeng Lu; Dafu Zhang; Hongwei Wu; Xiaoyan Zhen; Haorun Xue; Chao Meng; Shuting Chen; Xiao Yang; et al. (Arabian Journal of Geosciences, 2021)

Genomic molecular signatures determined characterization of Mycolicibacterium gossypii sp. nov., a fast-growing mycobacterial species isolated from cotton field soil - Rui-Rui Huang; Shen-Rong Yang; Cheng Zhen; Xian-Feng Ge; Xin-Kai Chen; Zhi-Qiang Wen; Ya-Nan Li; Wen-Zheng Liu (Antonie van Leeuwenhoek, 2021)

Ectobacillus aegiceratis sp. nov., a novel bacterium isolated from branch of Aegiceras corniculatum - Xiao-Hui Chen; Xiao-Rui Yan; Zi-Hao Huang; Ming-Sheng Chen; Li Tuo (Antonie van Leeuwenhoek, 2021)

Jiella mangrovi sp. nov., a novel endophytic bacterium isolated from leaf of Rhizophora stylosa - Ming-Sheng Chen; Fei-Na Li; Xiao-Hui Chen; Zi-Hao Huang; Xiao-Rui Yan; Li Tuo (Antonie van Leeuwenhoek, 2021)

Biodegradation of Di-n-butyl phthalate in rhizosphere and growth-promoting effect of Cucumis sativus Linn. by a novel Pseudomonas sp. DNB-S1 - Shuqin Li; Lei Wang; Ying Li; Fuxin Huang; Hui Yu; Ying Zhang; Rui Li; Zhaobo Chen; Ningrui Wei; Zhengzhe Yu (Ecotoxicology, 2021)

Phycicoccus avicenniae sp. nov., a novel endophytic actinomycete isolated from a branch of Avicennia mariana - Ming-Sheng Chen; Xiao-Hui Chen; Zi-Hao Huang; Xiao-Rui Yan; Li Tuo (Antonie van Leeuwenhoek, 2021)

Elevated pCO2 Impedes Succession of Phytoplankton Community From Diatoms to Dinoflagellates Along With Increased Abundance of Viruses and Bacteria - Ruiping Huang; Jiazhen Sun; Yunlan Yang; Xiaowen Jiang; Zhen Wang; Xue Song; Tifeng Wang; Di Zhang; He Li; Xiangqi Yi; Shouchang Chen; Nanou Bao; et al. (Frontiers in Marine Science, 2021)
Eutrophic coastal regions are highly productive and greatly influenced by human activities. Primary production supporting the coastal ecosystems is supposed to be affected by progressive ocean acidification driven by increasing CO 2 emissions. In order to investigate the effects of high p CO 2 (HC) on eutrophic plankton community structure and ecological functions, we employed 9 mesocosms and carried out an experiment under ambient (∼410 ppmv) and future high (1000 ppmv) atmospheric p CO 2 conditions, using in situ plankton community in Wuyuan Bay, East China Sea. Our results showed that HC along with natural seawater temperature rise significantly boosted biomass of diatoms with decreased abundance of dinoflagellates in the late stage of the experiment, demonstrating that HC repressed the succession from diatoms to dinoflagellates, a phenomenon observed during algal blooms in the East China Sea. HC did not significantly influence the primary production or biogenic silica contents of the phytoplankton assemblages. However, the HC treatments increased the abundance of viruses and heterotrophic bacteria, reflecting a refueling of nutrients for phytoplankton growth from virus-mediated cell lysis and bacterial degradation of organic matters. Conclusively, our results suggest that increasing CO 2 concentrations can modulate plankton structure including the succession of phytoplankton community and the abundance of viruses and bacteria in eutrophic coastal waters, which may lead to altered biogeochemical cycles of carbon and nutrients.

Improving rice eating and cooking quality by coordinated expression of the major starch synthesis-related genes, SSII and Wx, in endosperm - Lichun Huang; Zhengwen Gu; Zhuanzhuan Chen; Jiawen Yu; Rui Chu; Hongyan Tan; Dongsheng Zhao; Xiaolei Fan; Changquan Zhang; Qianfeng Li; Qiaoquan Liu (Plant Molecular Biology, 2021)

Long non-coding RNA NEAT1 promotes lipopolysaccharide-induced acute lung injury by regulating miR-424-5p/MAPK14 axis - Rui Zhang; Lina Chen; Fei Huang; Xiaorong Wang; Cuihong Li (Genes & Genomics, 2021)

Quantitative Proteomics Analysis of Sugarcane Ratoon Crop Chlorosis - Ye-Geng Fan; Rong-Fa Chen; Li-Hang Qiu; Zhong-Feng Zhou; Hui-Wen Zhou; Ji-Guang Wei; Xiu-Peng Song; Ting Luo; Prakash Lakshmanan; Xing Huang; Jian-Ming Wu; Yang-Rui Li (Sugar Tech, 2021)

Contrasting pathways of carbon sequestration in paddy and upland soils - Xiangbi Chen; Yajun Hu; Yinhang Xia; Shengmeng Zheng; Chong Ma; Yichao Rui; Hongbo He; Daoyou Huang; Zhenhua Zhang; Tida Ge; Jinshui Wu; Georg Guggenberger; et al. (Global Change Biology, 2021)
Paddy soils make up the largest anthropogenic wetlands on earth, and are characterized by a prominent potential for organic carbon (C) sequestration. By quantifying the plant‐ and microbial‐derived C in soils across four climate zones, we identified that organic C accrual is achieved via contrasting pathways in paddy and upland soils. Paddies are 39%–127% more efficient in soil organic C (SOC) sequestration than their adjacent upland counterparts, with greater differences in warmer than cooler climates. Upland soils are more replenished by microbial‐derived C, whereas paddy soils are enriched with a greater proportion of plant‐derived C, because of the retarded microbial decomposition under anaerobic conditions induced by the flooding of paddies. Under both land‐use types, the maximal contribution of plant residues to SOC is at intermediate mean annual temperature (15–20°C), neutral soil (pH~7.3), and low clay/sand ratio. By contrast, high temperature (~24°C), low soil pH (~5), and large clay/sand ratio are favorable for strengthening the contribution of microbial necromass. The greater contribution of microbial necromass to SOC in waterlogged paddies in warmer climates is likely due to the fast anabolism from bacteria, whereas fungi are unlikely to be involved as they are aerobic. In the scenario of land‐use conversion from paddy to upland, a total of 504 Tg C may be lost as CO 2 from paddy soils (0–15 cm) solely in eastern China, with 90% released from the less protected plant‐derived C. Hence, preserving paddy systems and other anthropogenic wetlands and increasing their C storage through sustainable management are critical for maintaining global soil C stock and mitigating climate change.

A functional chromogen gene C from wild rice is involved in a different anthocyanin biosynthesis pathway in indica and japonica - Weihua Qiao; Yanyan Wang; Rui Xu; Ziyi Yang; Yan Sun; Long Su; Lizhen Zhang; Junrui Wang; Jingfen Huang; Xiaoming Zheng; Shijia Liu; Yunlu Tian; et al. (Theoretical and Applied Genetics, 2021)

Temporal and spatial evolution patterns of drought in China over the past 500 years - Cuixia Wei; Bing Guo; Wenqian Zang; Fei Yang; Yuefeng Lu; Dafu Zhang; Hongwei Wu; Xiaoyan Zhen; Haorun Xue; Chao Meng; Shuting Chen; Xiao Yang; et al. (Arabian Journal of Geosciences, 2021)

Comparative Transcriptomic Analyses of Haemophilus parasuis Reveal Differently Expressed Genes among Strains with Different Virulence Degrees - Yuan Y. Zhou; Chao Wang; Jing Yuan; Rong L. Yin; Xin Chen; Rui Li; Xue L. Zhang; Jing Wang; Chen Huang; Rong H. Yin (Current Microbiology, 2021)

Association Between Blood Heavy Metal Concentrations and Dyslipidemia in the Elderly - Xingmeng Zhu; Yong Fan; Jie Sheng; Ling Gu; Qi Tao; Rui Huang; Kaiyong Liu; Linsheng Yang; Guimei Chen; Hongjuan Cao; Kaichun Li; Fangbiao Tao; et al. (Biological Trace Element Research, 2021)

Characterization of TEMPO-oxidized chitin nanofibers with various oxidation times and its application as an enzyme immobilization support - Rui Chen; Wen-Can Huang; Wei Wang; Xiangzhao Mao (Marine Life Science & Technology, 2021)

Cloning and expression analysis of hypoxia-related gene HO in cobia - Rui-tao Xie; Eric Amenyogbe; Wei-zheng Wang; Zhi-xiong Guo; Gang Chen; Jian-sheng Huang (Aquaculture International, 2021)

Effect of different industrial activities on soil heavy metal pollution, ecological risk, and health risk - Zhijie Long; Yi Huang; Wei Zhang; Zhangliang Shi; Daming Yu; Ying Chen; Chao Liu; Rui Wang (Environmental Monitoring and Assessment, 2021)

Reducible Fraction Dominates the Mobility of Vanadium in Soil Around an Iron Smelter - Long Zhijie; Huang Yi; Zhang Wei; Shi Zhangliang; Yu Daming; Chen Yin; Liu Chao; Wang Rui (Bulletin of Environmental Contamination and Toxicology, 2020)

Structural variability and niche differentiation of the rhizosphere and endosphere fungal microbiome of Casuarina equisetifolia at different ages - Rui Huang; Pan Chen; Xuan Wang; Huimin Li; Linzhi Zuo; Yaqian Zhang; Lei Li (Brazilian Journal of Microbiology, 2020)

Role of Chromatin Remodeling Genes and TETs in the Development of Human Midbrain Dopaminergic Neurons - Li Xiang; Guobin Huang; Wenjing Shu; Chunli Gong; Nan Cao; Rui Chen; Jixi Li; Hao Lu; Gaofeng Jiang (Stem Cell Reviews and Reports, 2020)

Ablation of olfactory bulb glutamatergic neurons induces depressive-like behaviors and sleep disturbances in mice - Mao-Yun Yuan; Ze-Ka Chen; Jian Ni; Tian-Xiao Wang; Shi-Yu Jiang; Hui Dong; Wei-Min Qu; Zhi-Li Huang; Rui-Xi Li (Psychopharmacology, 2020)

Reduction of heavy metals leaching and pore volume in high-volume fly ash cement pastes by adding nano-SiO2 - Qian Huang; Shuai Tang; Ya You; Yibo Chen; Haisen Deng; Rui Tian (Environmental Science and Pollution Research, 2020)

Long-term fertilization and intensive cropping enhance carbon and nitrogen accumulated in soil clay-sized particles of red soil in South China - Hu Xu; Kailou Liu; Wenju Zhang; Yichao Rui; Jingye Zhang; Lei Wu; Gilles Colinet; Qinghai Huang; Xianni Chen; Minggang Xu (Journal of Soils and Sediments, 2020)

Temporal variations in riverine hydrochemistry and estimation of the carbon sink produced by coupled carbonate weathering with aquatic photosynthesis on land: an example from the Xijiang River, a large subtropical karst-dominated river in China - Rui Yang; Hailong Sun; Bo Chen; Mingxing Yang; Qingrui Zeng; Cheng Zeng; Jie Huang; Huixian Luo; Danhui Lin (Environmental Science and Pollution Research, 2020)

Isolation of a novel strain Aspergillus niger WH-2 for production of l(+)-tartaric acid under acidic condition - Wenna Bao; Hongxiu Liao; Yi Chen; Qianqian Huang; Wendi Huang; Rui Fang; Shiwang Liu (Biotechnology Letters, 2020)

Effects of Exogenous GA3 and DPC Treatments on Levels of Endogenous Hormone and Expression of Key Gibberellin Biosynthesis Pathway Genes During Stem Elongation in Sugarcane - Li-Hang Qiu; Rong-Fa Chen; Han-Min Luo; Ye-Geng Fan; Xing Huang; Jun-Xian Liu; Fa-Qian Xiong; Hui-Wen Zhou; Chong-Kun Gan; Jian-Ming Wu; Yang-Rui Li (Sugar Tech, 2019)

TGF-β Secretion by M2 Macrophages Induces Glial Scar Formation by Activating Astrocytes In Vitro - Gongyu Song; Rui Yang; Qian Zhang; Long Chen; Dujuan Huang; Junwei Zeng; Changpei Yang; Tao Zhang (Journal of Molecular Neuroscience, 2019)

Benefit–risk assessment of commonly consumed fish species from South China Sea based on methyl mercury and DHA - Ping Wang; Shao-wei Chen; Zi-hui Chen; Wei-lun Huo; Rui Huang; Wei-xiong Huang; Jie-wen Peng; Xing-fen Yang (Environmental Geochemistry and Health, 2019)

Molecular Cloning and Expression Analysis of ScTUA Gene in Sugarcane - Bao-Qing Zhang; Min Shao; Yong-Jian Liang; Xing Huang; Xiu-Peng Song; Hu Chen; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2019)

Extended STIRPAT model-based driving factor analysis of energy-related CO2 emissions in Kazakhstan - Chuanhe Xiong; Shuang Chen; Rui Huang (Environmental Science and Pollution Research, 2019)

Ethylene, xylene, toluene and hexane are major contributors of atmospheric ozone in Hangzhou, China, prior to the 2022 Asian Games - Rui Feng; Qing Wang; Cheng-chen Huang; Jin Liang; Kun Luo; Jian-ren Fan; Hui-jun Zheng (Environmental Chemistry Letters, 2019)

Winter chemical partitioning of metals bound to atmospheric fine particles in Dongguan, China, and its health risk assessment - Lin Huang; Yun-He Bai; Rui-Yue Ma; Ze-Ming Zhuo; Ling Chen (Environmental Science and Pollution Research, 2019)

Development of a colloidal gold-based immunochromatographic strip for rapid detection of Rice stripe virus - De-qing Huang; Rui Chen; Ya-qin Wang; Jian Hong; Xue-ping Zhou; Jian-xiang Wu (Journal of Zhejiang University-SCIENCE B, 2019)

Health Risk Assessment for Local Residents from the South China Sea Based on Mercury Concentrations in Marine Fish - Shao-wei Chen; Zi-hui Chen; Ping Wang; Rui Huang; Wei-lun Huo; Wei-xiong Huang; Xing-fen Yang; Jie-wen Peng (Bulletin of Environmental Contamination and Toxicology, 2018)

Characterization of clinical features and outcome for human-to-human transmitted severe fever with thrombocytopenia syndrome - Bei Jia; Weihua Wu; Rui Huang; Guiyang Wang; Peixin Song; Yang Li; Yong Liu; Yali Xiong; Xiaomin Yan; Yingying Hao; Juan Xia; Zhaoping Zhang; et al. (Infectious Diseases, 2018)

A single nucleotide mutation of IspF gene involved in the MEP pathway for isoprenoid biosynthesis causes yellow-green leaf phenotype in rice - Rui Huang; Yang Wang; Pingrong Wang; Chunmei Li; Fuliang Xiao; Nenggang Chen; Na Li; Caixia Li; Changhui Sun; Lihua Li; Rongjun Chen; Zhengjun Xu; et al. (Plant Molecular Biology, 2018)

Foliar application with nano-silicon reduced cadmium accumulation in grains by inhibiting cadmium translocation in rice plants - Rui Chen; Changbo Zhang; Yanling Zhao; Yongchun Huang; Zhongqi Liu (Environmental Science and Pollution Research, 2018)

Regional disaster risk evaluation of China based on the universal risk model - Lu Chen; Yue-cheng Huang; Rui-zhen Bai; An Chen (Natural Hazards, 2017)

Creation of miniature pig model of human Waardenburg syndrome type 2A by ENU mutagenesis - Tang Hai; Weiwei Guo; Jing Yao; Chunwei Cao; Ailing Luo; Meng Qi; Xianlong Wang; Xiao Wang; Jiaojiao Huang; Ying Zhang; Hongyong Zhang; Dayu Wang; et al. (Human Genetics, 2017)

Genome re-sequencing analysis uncovers pathogenecity-related genes undergoing positive selection in Magnaporthe oryzae - Jidong Cao; Yongqi Yu; Junkai Huang; Rui Liu; Yan Chen; Suiyan Li; Jun Liu (Science China Life Sciences, 2017)

Comparison of dust emissions, transport, and deposition between the Taklimakan Desert and Gobi Desert from 2007 to 2011 - SiYu Chen; JianPing Huang; JingXin Li; Rui Jia; NanXuan Jiang; LiTai Kang; XiaoJun Ma; TingTing Xie (Science China Earth Sciences, 2017)

A Shinella β-N-acetylglucosaminidase of glycoside hydrolase family 20 displays novel biochemical and molecular characteristics - Junpei Zhou; Zhifeng Song; Rui Zhang; Caihong Chen; Qian Wu; Junjun Li; Xianghua Tang; Bo Xu; Junmei Ding; Nanyu Han; Zunxi Huang (Extremophiles, 2017)

Role of the SPS Gene Families in the Regulation of Sucrose Accumulation in Sugarcane - Dong-Liang Huang; Cui-Xian Qin; Yi-Yun Gui; Li-Han Zhao; Zhong-Liang Chen; Miao Wang; Yue Sun; Qing Liao; Yang-Rui Li; Prakash Lakshmanan (Sugar Tech, 2017)

Effects of DDIT4 in Methamphetamine-Induced Autophagy and Apoptosis in Dopaminergic Neurons - Bing Li; Rui Chen; Ling Chen; Pingming Qiu; Xiuyun Ai; Enping Huang; Weiye Huang; Chuanxiang Chen; Chao Liu; Zhoumeng Lin; Wei-Bing Xie; Huijun Wang (Molecular Neurobiology, 2017)

Warming Effects on Ecosystem Carbon Fluxes Are Modulated by Plant Functional Types - Ji Chen; Yiqi Luo; Jianyang Xia; Kevin R. Wilcox; Junji Cao; Xuhui Zhou; Lifen Jiang; Shuli Niu; Katerina Y. Estera; Rujin Huang; Feng Wu; Tafeng Hu; et al. (Ecosystems, 2017)

Computation of satellite clock–ephemeris corrections using a priori knowledge for satellite-based augmentation system - Jie Chen; Zhigang Huang; Rui Li (GPS Solutions, 2017)

Erratum to: Glycogen synthase kinase 3 (GSK3)-inhibitor SB216763 promotes the conversion of human umbilical cord mesenchymal stem cells into neural precursors in adherent culture - Liyang Gao; Mingyan Zhao; Peng Li; Junchao Kong; Zhijun Liu; Yonghua Chen; Rui Huang; Jiaqi Chu; Juanhua Quan; Rong Zeng (Human Cell, 2017)

Glycogen synthase kinase 3 (GSK3)-inhibitor SB216763 promotes the conversion of human umbilical cord mesenchymal stem cells into neural precursors in adherent culture - Liyang Gao; Mingyan Zhao; Peng Li; Junchao Kong; Zhijun Liu; Yonghua Chen; Rui Huang; Jiaqi Chu; Juanhua Quan; Rong Zeng (Human Cell, 2017)

The destruction box is involved in the degradation of the NTE family proteins by the proteasome - Fei-Fei Huang; Ping-An Chang; Lan-Xi Sun; Wen-Zhen Qin; Li-Ping Han; Rui Chen (Molecular Biology Reports, 2016)

Transcriptome of High-Sucrose Sugarcane Variety GT35 - Dong-Liang Huang; Yi-Jing Gao; Yi-Yun Gui; Zhong-Liang Chen; Cui-Xian Qin; Miao Wang; Qing Liao; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2016)

Molecular Design, Structural Analysis and Antifungal Activity of Derivatives of Peptide CGA-N46 - Rui-Fang Li; Zhi-Fang Lu; Ya-Nan Sun; Shi-Hua Chen; Yan-Jie Yi; Hui-Ru Zhang; Shuo-Ye Yang; Guang-Hai Yu; Liang Huang; Chao-Nan Li (Interdisciplinary Sciences: Computational Life Sciences, 2016)

Optimization of the Expression Conditions of CGA-N46 in Bacillus subtilis DB1342(p-3N46) by Response Surface Methodology - Rui-Fang Li; Bin Wang; Shuai Liu; Shi-Hua Chen; Guang-Hai Yu; Shuo-Ye Yang; Liang Huang; Yan-Li Yin; Zhi-Fang Lu (Interdisciplinary Sciences: Computational Life Sciences, 2016)

Assessing spatial likelihood of flooding hazard using naïve Bayes and GIS: a case study in Bowen Basin, Australia - Rui Liu; Yun Chen; Jianping Wu; Lei Gao; Damian Barrett; Tingbao Xu; Linyi Li; Chang Huang; Jia Yu (Stochastic Environmental Research and Risk Assessment, 2016)

Transcriptome analysis reveals translational regulation in barley microspore-derived embryogenic callus under salt stress - Cheng-hong Liu; Rui-ju Lu; Gui-mei Guo; Ting He; Ying-bo Li; Hong-wei Xu; Run-hong Gao; Zhi-wei Chen; Jian-hua Huang (Plant Cell Reports, 2016)

A new flavane acid from the fruits of Illicium verum - Liang-Deng Wu; Chun-Lan Xiong; Zi-Zhan Chen; Rui-Jie He; Yan-Jun Zhang; Yan Huang; Sheng-Ping Deng; Rui-Yun Yang; Jun Li (Natural Product Research, 2016)

Isolation and Expression Analysis of Sucrose Synthase Gene (ScSuSy4) from Sugarcane - Zhong-Liang Chen; Yi-Yun Gui; Cui-Xian Qin; Miao Wang; Qing Liao; Dong-Liang Huang; Yang-Rui Li (Sugar Tech, 2016)

Immunogenicity of transmissible gastroenteritis virus (TGEV) M gene delivered by attenuated Salmonella typhimurium in mice - Ying Qing; Jiawen Liu; Xiaobo Huang; Yaqing Li; Yudi Zhang; Jie Chen; Xintian Wen; Sanjie cao; Yiping Wen; Rui Wu; Qigui Yan; Xiaoping Ma (Virus Genes, 2016)

Erratum to: First molecular detection of porcine circovirus type 2 in bovids in China - Shao-Lun Zhai; Rui-Ai Chen; Sheng-Nan Chen; Xiao-Hui Wen; Dian-Hong Lv; Da-Cheng Wu; Jie Yuan; Zhong Huang; Xiu-Rong Zhou; Man-Lin Luo; Dong-Sheng He; Wen-Kang Wei (Virus Genes, 2016)

Notch2 signaling contributes to cell growth, invasion, and migration in salivary adenoid cystic carcinoma - Jing Qu; Min Song; Jian Xie; Xiao-Yu Huang; Xiao-Meng Hu; Rui-Huan Gan; Yong Zhao; Li-Song Lin; Jiang Chen; Xu Lin; Da-Li Zheng; You-Guang Lu (Molecular and Cellular Biochemistry, 2016)

GRY79 encoding a putative metallo-β-lactamase-trihelix chimera is involved in chloroplast development at early seedling stage of rice - Chunmei Wan; Chunmei Li; Xiaozhi Ma; Yang Wang; Changhui Sun; Rui Huang; Ping Zhong; Zhiyan Gao; Dan Chen; Zhengjun Xu; Jianqing Zhu; Xiaoling Gao; et al. (Plant Cell Reports, 2015)

The concentration of selenium matters: a field study on mercury accumulation in rice by selenite treatment in qingzhen, Guizhou, China - Yu-Feng Li; Jiating Zhao; Yunyun Li; Hanjun Li; Junfang Zhang; Bai Li; Yuxi Gao; Chunying Chen; Manyi Luo; Rui Huang; Jun Li (Plant and Soil, 2015)

Long-Term Effectiveness of Total Hip Replacement with the Collum Femoris Preserving Prosthesis - Rui-jin You; Wen-zhong Zheng; Kun Chen; Hong-sheng Lv; Dian-feng Huang; Yi-zeng Xiao; De-yu Yang; Zhai-quan Su (Cell Biochemistry and Biophysics, 2015)

Effects of Exogenous Abscisic Acid on Cell Membrane and Endogenous Hormone Contents in Leaves of Sugarcane Seedlings under Cold Stress - Xing Huang; Ming-Hui Chen; Li-Tao Yang; Yang-Rui Li; Jian-Ming Wu (Sugar Tech, 2015)

Optimization of the expression conditions of CGA-N46 in Bacillus subtilis DB1342(p-3N46) by response surface methodology - Rui-Fang Li; Bin Wang; Shuai Liu; Shi-Hua Chen; Guang-Hai Yu; Shuo-Ye Yang; Liang Huang; Yan-Li Yin; Zhi-Fang Lu (Interdisciplinary Sciences: Computational Life Sciences, 2015)

Effect of Trash Addition to the Soil on Microbial Communities and Physico-Chemical Properties of Soils and Growth of Sugarcane Plants - Qing Liao; Guang-Po Wei; Gui-Fen Chen; Bin Liu; Dong-Liang Huang; Yang-Rui Li (Sugar Tech, 2014)

First molecular detection of porcine circovirus type 2 in bovids in China - Shao-Lun Zhai; Rui-Ai Chen; Sheng-Nan Chen; Xiao-Hui Wen; Dian-Hong Lv; Da-Cheng Wu; Jie Yuan; Zhong Huang; Xiu-Rong Zhou; Man-Lin Luo; Dong-Sheng He; Wen-Kang Wei (Virus Genes, 2014)

A new naphthol from the twigs and leaves of Pterospermum yunnanense - Haoliang Li; Guoli Huang; Bo Liu; Ying Liu; Rui Zhan; Yegao Chen (Natural Product Research, 2014)

Piromelatine exerts antinociceptive effect via melatonin, opioid, and 5HT1A receptors and hypnotic effect via melatonin receptors in a mouse model of neuropathic pain - Yuan-Yuan Liu; Dou Yin; Li Chen; Wei-Min Qu; Chang-Rui Chen; Moshe Laudon; Neng-Neng Cheng; Yoshihiro Urade; Zhi-Li Huang (Psychopharmacology, 2014)

Anti-depressive activities and biotransformation of timosaponin B-III and its derivatives - WeiXin Jiang; Jing Guo; Rui Xue; KaiCheng Zhu; ZhiXiong Li; MingCang Chen; ChengGang Huang (Natural Product Research, 2014)

Serum uric acid level is associated with the prevalence but not with survival of amyotrophic lateral sclerosis in a Chinese population - Zhenzhen Zheng; Xiaoyan Guo; Qianqian Wei; Wei Song; Bei Cao; Rui Huang; Ruwei Ou; Xueping Chen; Huifang Shang (Metabolic Brain Disease, 2014)

Effects of Sub-soil Drip Fertigation on Sugarcane in Field Conditions - Gui-Fen Chen; Qi-Zhan Tang; Yang-Rui Li; Yu-Yi Huang; Bin Liu; Lin Xu; Hai-Rong Huang (Sugar Tech, 2012)

Association of interleukin 23 receptor gene polymorphisms (rs10489629, rs7517847) with rheumatoid arthritis in European population: a meta-analysis - Yu Zhai; Ke Xu; Fen Huang; Hui Peng; Chen-Chen Feng; Kao-Kao Zhu; Rui-Xue Leng; Hai-Feng Pan; Dong-Qing Ye (Molecular Biology Reports, 2012)

Determination of Geometrical and Structural Representative Volume Elements at the Baihetan Dam Site - Wen Zhang; Jian-ping Chen; Chang Liu; Rui Huang; Ming Li; Ying Zhang (Rock Mechanics and Rock Engineering, 2012)

Gene expression profiling of Sinapis alba leaves under drought stress and rewatering growth conditions with Illumina deep sequencing - Cai-Hua Dong; Chen Li; Xiao-Hong Yan; Shun-Mou Huang; Jin-Yong Huang; Li-Jun Wang; Rui-Xing Guo; Guang-Yuan Lu; Xue-Kun Zhang; Xiao-Ping Fang; Wen-Hui Wei (Molecular Biology Reports, 2012)

Implication of genetic variants near TMEM18, BCDIN3D/FAIM2, and MC4R with coronary artery disease and obesity in Chinese: a angiography-based study - Hao Huang; Zhi Zeng; Li Zhang; Rui Liu; Xian Li; Ou Qiang; Yucheng Chen (Molecular Biology Reports, 2012)

Localized Delivery of Antisense Oligonucleotides by Cationic Hydrogel Suppresses TNF-α Expression and Endotoxin-Induced Osteolysis - Lei Dong; Zhen Huang; Xing Cai; Jiawei Xiang; Yi-An Zhu; Rui Wang; Jiangning Chen; Junfeng Zhang (Pharmaceutical Research, 2011)

Molecular phylogeny of Ranunculaceae based on rbc L sequences - Ying-fan Cai; Sheng-wei Li; Min Chen; Ming-feng Jiang; Yi Liu; Yong-fang Xie; Quan Sun; Huai-zhong Jiang; Neng-wen Yin; Ling Wang; Rui Zhang; Cheng-lin Huang; et al. (Biologia, 2010)

Sequence and expression analysis of the gene encoding inducible cAMP early repressor in tilapia - Ming Chen; Rui Wang; Xi Gan; Aiying Lei; Chao Li; Xiaoli Yu; Jun Huang; Ting Huang; Wanwen Liang (Molecular Biology Reports, 2010)

Inhibitor of DNA binding-1 promotes the migration and proliferation of endothelial progenitor cells in vitro - Hong Wang; Yang Yu; Rui-wei Guo; Yan-kun Shi; Ming-bao Song; Jian-fei Chen; Shi-yong Yu; Yang-guang Yin; Pan Gao; Lan Huang (Molecular and Cellular Biochemistry, 2010)

Protective effect of DNA-mediated immunization with liposome-encapsulated GRA4 against infection of Toxoplasma gondii - Rui Chen; Shao-hong Lu; Qun-bo Tong; Di Lou; Dong-yan Shi; Bing-bing Jia; Guo-ping Huang; Jin-fu Wang (Journal of Zhejiang University-SCIENCE B, 2009)

TRANSPARENT TESTA 12 genes from Brassica napus and parental species: cloning, evolution, and differential involvement in yellow seed trait - You-Rong Chai; Bo Lei; Hua-Lei Huang; Jia-Na Li; Jia-Ming Yin; Zhang-Lin Tang; Rui Wang; Li Chen (Molecular Genetics and Genomics, 2009)

Adenovirus-mediated PDCD5 gene transfer sensitizes K562 cells to apoptosis induced by idarubicin in vitro and in vivo - Guo-Rui Ruan; Hong-Shan Zhao; Yan Chang; Jin-Lan Li; Ya-Zhen Qin; Yan-Rong Liu; Shan-Shan Chen; Xiao-Jun Huang (Apoptosis, 2008)

Prohibitin suppresses renal interstitial fibroblasts proliferation and phenotypic change induced by transforming growth factor-β1 - Wei Guo; Hong Xu; Jing Chen; Yong Yang; Jia Wei Jin; Rui Fu; Hai Mei Liu; Xi Liang Zha; Zhi Gang Zhang; Wen Yan Huang (Molecular and Cellular Biochemistry, 2007)